GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 703595859 species occurrences available in GBIF matching the query: All data. The dataset includes 703595859 records from 14974 constituent datasets: 8391 records from SBT-Living. 8857 records from Artròpodes d'Andorra. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 1 records from Oribates calcaratus. 852 records from Estructura poblacional, variación genética y conservación de tres especies del género Pinus, endémicas de México. 17618 records from BioGIS - Mammals - INPA database. 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 5414 records from Ontario BioBlitz Species Records. 133 records from Schellenberg A. 1936. The fishery grounds near Alexandria. 10. Amphipoda Benthonica. Notes and memoirs no 11. 3 records from A new species of Lyssomanes Hentz, 1845 from Brazil (Araneae: Salticidae). 71 records from (Data S1) Palynology of ODP Site 113-696. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 13 records from FND "Weißer Berg" Leißling. 1 records from Waldtag in und um Seelingstädt. 138 records from Total foraminifera counts of multinet M10/2_MSN297. 21 records from Nannofossil abundance of Hole 6-55. 3 records from Nannofossil abundance of Hole 31-301. 3 records from Nannofossil abundance of Hole 94-609A. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 1218 records from (Table 6) Relative abundances of the seven species of planktonic foraminifera from ODP Site 108-662. 578 records from (Table 3) Relative abundances of selected planktonic foraminifera of ODP Site 117-722. 14137 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 313949 records from United States National Plant Germplasm System Collection. 117 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 3 records from Analyses of the recent components of sediment core PS1215-2. 19 records from Occurrence of mammalia relicts at site Gröbern. 48 records from Occurrence of mammalia relicts at site Falkensteinhöhle. 164 records from Planktic foraminifera abundance of Hole 22-215. 176 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 156 records from Dinoflagellate cysts of mooring MST-9 (station 915) with cell content. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 209 records from Relative abundance of coccosphere-units at site GIK23414. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 818 records from Range chart of calcareous nannofossils from ODP Hole 188-1165B (Table 1). 746 records from RMT Trawl catch from the 1986/87 V7 AAMBER voyage. 558 records from (Table 5) Pleistocene ostracodes from ODP Hole 104-644A. 1134 records from Ictiofauna de los corredores biológicos Sierra Madre del Sur y Selva Maya Zoque. 423 records from Bird Collection of Otto Hedin. 274 records from Foraminifera abundance of sediment core BM1958.631. 780 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 12 records from Abundance of microplankton from bottle APRIL-2000-K4. 126 records from Planktic foraminifera abundance of Hole 32-305. 962 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 117 records from Wassermann. 73 records from VFD-HH/SH: Pferdweide Lammert. 1770 records from Schmidt Museum of Natural History_Birds. 22 records from Phytoplankton abundance at bottle station GOM6/1. 95 records from BIRDRACE BiBi. 126 records from Total foraminifera counts from M35/1_MSN1050. 6 records from Wiese. 451 records from Nannofossil abundance of Hole 15-148. 3910 records from Plant (MNHM-PL). 1972 records from (Figure 6) Distribution chart of benthic foraminifers in ODP Site 126-792. 2427 records from Ibaraki Nature Museum, Mollusk collection. 1 records from Occurrence of mammalia relicts at site Kleine Feldhofer Grotte. 26 records from Planktic foraminifera abundance of Hole 20-200A. 394 records from Range table from benthic foraminifers in ODP Hole 144-871C. 769 records from Range table from benthic foraminifers in ODP Hole 145-883B. 169 records from Whale log - observations from ANARE voyages. 45 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 104 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 19 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 16 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 61 records from Fürstenberger Ralley Teil 3. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 128 records from Total foraminifera counts of multinet M33/1_MSN1030. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-18-1. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 11 records from Zoobenthos in surface sediments off Cape Lucul. 49 records from Pollen profile form Hickory Ridge Basin, Illinois, U.S.A. 16 records from Coccolith counts of multinet M32/5_MSN986. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/046-3. 131 records from (Table 3) Occurrence of benthic foraminifera in the Ledyanaya section. 1691 records from (Table 3) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-707A. 109504 records from Plant Specimens of Kurashiki Museum of Natural History. 13225 records from Colección de Mamíferos del Museo de Zoología 'Alfonso L . Herrera', México (MZFC, UNAM). 646 records from Engraulidae-Clupeidae. Report on the Danish Oceanographical Expeditions 1908-1910 to the Mediterranean and adjacent seas. 108 records from Occurrence of mammalia relicts at site l´Abri du Flageolet I. 68 records from Planktic foraminifera abundance of Hole 22-213. 89762 records from Ornitho.eus. 1 records from Zetes latirostris. 93 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cotingidae. 14 records from Contribution to the knowledge of Neoperla (Plecoptera: Perlidae) from Hainan Province of China. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/090-4. 75655 records from Ibaraki Nature Museum, Vascular Plants collection. 15586 records from Historical quantitative benthos grab samples from the Southern Baltic Sea (EurOBIS). 97 records from CNIN/Tipos Hymenoptera. 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 320 records from Range table from planktonic foraminifers in ODP Hole 141-863A. 400 records from Phytoplankton abundance in surface water in October 1997, Callao, Peru. 627 records from Inventario forestal en bosques dominados por encino (Quercus Fagaceae) en la Sierra de Manantlán, Jalisco-Colima, México: Descripción de los patrones de respuesta al medio físico y biológico. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 62 records from Plasm bearing foraminifera counts of multinet M21/5_MSN728. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 114 records from Contribution to the knowledge of the genus Singilis Rambur, 1837 of Africa (Coleoptera: Carabidae: Lebiini). Part IV. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 1 records from Zetes semirufus. 17 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB04 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 163 records from Planktic foraminifera abundance of Hole 32-313. 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 1494 records from CSIRO, Cruise SS200001, Marine Biodiversity, South and Southeast Australia, 2001. 315232 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 33 records from Range table from planktonic foraminifers in ODP Hole 175-1078B. 240 records from Range table from benthic foraminifers in ODP Hole 175-1075A. 5 records from Two new endemic species of Epictia Gray, 1845 (Serpentes: Leptotyphlopidae) from Northern Peru. 3 records from Microfossil abundance of Hole 50-415. 2 records from Abundance of benthos infauna at station GIK23025-2. 162150 records from Ditsong National Museum of Natural History Collection: 1805-2008. 20 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2004. 496 records from 2000-2003 RBWM WHS Surveys. 1849 records from National Trust - Heigham Holmes species data held by The National Trust. 101 records from MVZ Mammal Observations (Arctos). 1207 records from Calcareous nanofossils in late Pliocene sediments of ODP Site 162-982. 3204 records from Faunal Inventory of Morysin Nature Reserve. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 11 records from Three new species and redescription of the type species of Soesilarishius Makhan, 2007 (Araneae: Salticidae: Euophryini). 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 4 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 105 records from BIRDRACE coesfelder_vogelkundler. 430 records from (Appendix 6) Benthic foraminifera at termination I in sediment core GIK23068-3 in the Norwegian Sea. 357 records from Abundance of benthic foraminiferal taxa for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 110 records from Abundance of planktic foraminifera at CTD station M39/4_366CTD-22. 177466 records from CAS Entomology (ENT). 374 records from Diversidad y distribución del género Tripsacum (Poaceae: Tripsacinae) en México. 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 87 records from Plasm bearing foraminifera counts from M35/1_MSN1049. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 1842 records from Importancia de las lombrices de tierra (Oligochaeta) en el monitoreo de áreas prioritarias de conservación del centro, este y sureste de México. 28 records from Occurrence of mammalia relicts at site Climauti II. 525 records from Planktic foraminifera abundance of Hole 94-609. 34140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 3860 records from (Appendix Table 1) Absolute abundances of benthic foraminifers in DSDP Hole 94-608. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-014. 85783 records from Birds (KIEE-BI). 463 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 37641 records from Nordic Genetic Resources. 3634 records from Herpetological collection of National Museum of Nature and Science. 1161 records from CNIN/Triatominos (Hemiptera-Heteroptera-Reduviidae). 398 records from Mooswald (Freiburg). 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 72 records from Faunal assemblage of sediment core TR149-35. 66 records from Plasm bearing foraminifera counts of multinet M21/2_MSN642. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 535 records from Distribution of microorganisms in recent sediments of Kiel Bay. 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 8980 records from MEXU/Tipos de plantas vasculares. 5233 records from (Appendix A) Stable carbon and oxygen isotopes and paleoproductivity reconstructions for the last 550 kyr of ODP Hole 130-807A from the Ontong Java Plateau, Pacific Ocean. 80 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 1. 347088 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 2403 records from ZUEC-AVE - Coleção de Aves do Museu de Zoologia da UNICAMP. 59 records from A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae). 4872 records from Abundance and diversity of the Amphipoda (Crustacea) from the Greenlandic shelf. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 26 records from A revision of the western hemisphere Chalcoscirtus (Araneae: Salticidae). 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 2 records from Amphibia ZMK. 10 records from Ecología de jaguares y pumas en el oeste de México: Fase II. 101 records from Birdrace-Herford-Birder-Herford. 881 records from Moluscos Marinhos de Augusto Nobre. 718 records from HSU Vertebrate Museum Amphibian Collection. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 45 records from (Table 8) Pliocene nannofossil range chart for ODP Hole 134-833B. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/508-2. 106100 records from Fish (NSMK-PI). 43590 records from Computarización de la colección de abejas (Hymenoptera: Apoidea) del Museo de Zoología Alfonso L. Herrera, de la Facultad de Ciencias de la UNAM. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 877 records from Benthic foraminifera distribution of sediment core ASV11-987 (ASV987). 257 records from Kernberge und Umgebung (Jena). 1 records from Occurrence of mammalia relicts at site Ballybetagh. 2357 records from Foraminifera abundance of Hole 17-167. 260102 records from R. L. McGregor Herbarium Vascular Plants Collection. 161 records from A conspectus of the native and naturalized species of Nephrolepis (Nephrolepidaceae) in the world. 142 records from Filogeografía y recursos genéticos de las vainillas de México. 1116766 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 30 records from (Table 2) Benthic isopod species of the Ross Sea, their bathymetry and distribution in the Southern Ocean. 2 records from The Genus Criodion (Audinet-Serville, 1833) (Coleoptera, Cerambycidae): First Record for Panama. 233224 records from MVZ Mammal Collection (Arctos). 119366 records from The digitization of plant specimens of NTU. 35 records from Gym Freyung. 431 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M44/3_KL83 from the middle bathyal of the eastern Levantine Basin. 26 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 35693 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2002) (AfrOBIS). 88 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 14 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 18 records from Meiofauna abundance in sediment core 13368-015. 10 records from Benthic macrofauna abundance of sediment core 13078-017. 308 records from Planktic foraminifera counts of sediment core V19-178. 234 records from Phytoplankton samples - 2006/07 V3 SAZ-Sense. 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 31082 records from MEXU/Plantas Vasculares. 16425 records from Coleção Entomológica Pe. Jesus Santiago Moure (Hymenoptera). 82953 records from Vascular Plants, Observations, Oslo (O). 29 records from Klimaoasen in Köln. 46 records from An der Ohm, (Wettsaasen). 1351 records from Neogene palynomorpha from site 93-603, part 1. 83 records from Planktic foraminifera abundance of Hole 14-135. 1 records from Planktic foraminifera abundance of Hole 8-72. 3119 records from Hormigas en cultivos de naranja (Citrus sinensis (L.) Osbeck) de la costa Caribe de Colombia. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 2259 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 70 records from Exotic terrestrial flatworms, Macquarie Island. 12 records from Abundance of epibenthic echinoderms at seafloor photography station M21/5_317. 8 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 306 records from Camera trap database of Tiger from Rajaji National Park, Uttarakhand. 1639 records from Avena wild species collection. (N.I.Vavilov Institute of Plant Genetic Resources (VIR)). 1798 records from Insect (KDIR-IN). 403 records from (Appendix A) Relative abundance of Emiliania huxleyi in sediment cores of the North Atlantic. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 2 records from Description of a new genus and two new species of alpheid shrimps from Guam (Crustacea, Decapoda) *. 2 records from A remarkable new flightless Madrasostes Paulian, 1975 from Vietnam (Coleoptera Scarabaeoidea Hybosoridae Ceratocanthinae). 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 15 records from AKG-Bensheim. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 178 records from Total foraminifera counts of multinet M6/7_MSN148. 3000 records from Colección Macroinvertebrados Acuáticos Universidad Católica de Oriente. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-9. 7 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 1 records from Miriapodi di alcune grotte della Campania. 976 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-075. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 18822 records from Mycology herbarium, NTNU University Museum. 1115 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 16 records from Redescriptions and new host records of chewing lice of the genus Ricinus (Phthiraptera: Ricinidae) from the Neotropical Region. 30 records from Benthic foraminifera abundance of Hole 42-379A. 899 records from (Fig. 13) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 80-549 in the North Atlantic. 4 records from Tropidomyrmex elianae, a new myrmicine ant genus and species from Brazil, tentatively assigned to Solenopsidini (Hymenoptera, Formicidae).. 224432 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 20 records from Mikroorganismen. 48 records from Wahner Heide LK 12 Biologie. 6 records from Benthic macrofauna abundance of sediment core 13077-019. 31 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-18. 210 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 734 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Icteridae. 22625 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 2563453 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 164 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 906 records from Digital Florula - Las Cruces Biological Station. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 2233 records from Chrysomelidae of Poland. 92 records from Total foraminifera counts of multinet M26/1_MSN845. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 133 records from Total foraminifera counts of multinet PO247/2_MSN1381. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 2 records from Kirchenforst. 22 records from Nannofossil abundance of Hole 9-83A. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 100 records from (Table 4) Distribution of nannofossils in DSDP Hole 87-583D. 10 records from Benthic macrofauna abundance of sediment core 12930-044. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 14202 records from Plant specimens of Hokkaido University Museum. 13736 records from MfN - Mallophaga Collection. 401 records from Range table from planktonic foraminifers in ODP Hole 138-852B. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 10121 records from Arachnologie - SMNG. 1092 records from Field Study Group of the Dutch Mammal Society (NL) - 2009 - Mammal Survey Serra da Estrela, Portugal. 3711 records from Florida Keys Reef Visual Census 2004. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 32450 records from Naturalis National Natural History Museum (NL) – Invertebrate specimens from marine expeditions. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 3 records from A new species of the genus Meganola Dyar, 1898 (Lepidoptera, Nolidae, Nolinae) from China. 6258 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 1 records from Zetes ephippiatus. 16 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 10 records from Ice Amphipods Canada Basin. 501 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 13478 records from Herp Collection. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 1968 records from (Appendix B) Distribution of planktonic foraminifera at DSDP Hole 72-518. 66 records from Foraminifera abundance of Hole 55-432A. 53 records from Planktic foraminifera abundance of Hole 29-281A. 102 records from Range table from planktonic foraminifers in ODP Hole 169-1035D. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 1 records from Results of palynological analysis of Hole 302-M0004C. 2670 records from Colección Teriológica y Ornitológica de la Universidad Tecnológica del Chocó. 11 records from Collection Xiphosura SMF. 89 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (75° N section). 4 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 73 records from Fossil (JNHM-FO). 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 97 records from LauWi. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 114 records from BIRDRACE VIE will rock you!. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN649. 15 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_13-CTD162. 43 records from Schulgelände Thurmair-Gymnasium. 15 records from Two new species of Philopteroides (Phthiraptera: Ischnocera: Philopteridae) of the beckeri species-group, from New Guinean painted berrypeckers (Aves: Passeriformes: Paramythiidae). 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 4 records from Counts (3) of calcareous dinocysts along profile Stevns-Klint. 30 records from Nannofossil abundance of Hole 8-71. 18 records from Benthic macrofauna abundance of sediment core 13201-002. 271 records from Planktic foraminifera counts of sediment core RC11-147. 3023 records from Flora y datos básicos para la evaluación de las actividades apícola y forestal en tres áreas focales del corredor Sian Ka'an-Calakmul. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 7076556 records from Great Backyard Bird Count. 30302 records from Arizona State University Amphibian and Reptile Collection. 5159 records from CNHE/Coleccion Nacional de Helmintos. 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 83 records from Fiocruz/COLPROT - Coleção de Protozoários. 1728 records from CASES: The pre-winter assemblages of southeastern Beaufort Sea. 24 records from Distribución, abundancia, estructura poblacional y potencial reproductor de Zamia furfuracea L.. 21 records from Phytoplankton abundance at the sea bottom off Sechura in january 2007, Peru. 2268 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-173-3. 96 records from Range table from planktonic foraminifers in ODP Hole 182-1126D. 852 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_88MC. 135 records from Total foraminifera counts of multinet M11/1_MSN522. 64 records from Feuchtbiotop Weidenkaule. 1726 records from KTU Pinophyta. 9 records from Nannofossil abundance of Hole 60-455. 176 records from paleovertebrados. 2019 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 1069 records from ZFMK Sound Archive. 1 records from A NEW SPECIES OF DRY FOLIAGE MIMICKING Eriovixia ARCHER, 1951 FROM CENTRAL WESTERN GHATS, INDIA (ARANEAE: ARANEIDAE). 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 6 records from Phytoplankton abundance at station Rigel_1_2005-03 in March 2005, Chipana, Chile. 566 records from (Appendix A1) Distribution of benthic foraminifera in ODP Site 184-1143. 43 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV30_1. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 1512 records from tree climbing bryophytes & lichens at tree base and crown with traits. 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 105 records from Plasm bearing foraminifera counts of multinet M21/5_MSN731. 569 records from (Appendix A) Planktonic foraminiferal abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-06-2. 115 records from Nannofossil abundance of Hole 29-279A. 21 records from Nannofossil abundance of Hole 24-232A. 56 records from Nannofossil abundance of Hole 94-607. 81 records from Colección de Referencia de Poliquetos del Museo de Ciencias de la Universidad El Bosque. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-087. 15 records from Benthic macrofauna abundance of sediment core 13078-013. 9852 records from ZUEC-LEP - Coleção de Lepidoptera do Museu de Zoologia da UNICAMP. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 49 records from Abundance of calcareous nannofossils across the K/T boundary at ODP Hole 113-690C (Table 1). 2070 records from (Table 4) Plio-Pleistocene benthic foraminifera of ODP Hole 107-652A. 998 records from Korean Ethnobotany Database. 22 records from Sediment properties of core PLG95B_06BOXG. 448 records from Harpactus Shuckard. 131 records from Unser Schulhof - eine Apotheke. 67 records from Occurrence of mammalia relicts at site l´Abri des Battuts I. 2 records from Benthic foraminifera abundance of Hole 42-376. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 12 records from Ficha de Sonora aemula. 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 3761 records from Mountain Invasion Research Network (MIREN) survey. 61234 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1999) (AfrOBIS). 195264 records from U.S.D.A. Forest Service, Redwood Sciences Laboratory - Lamna Point Count. 2128 records from Universitat de València, Colecciones de Criptógamas: VAL_Algae. 48 records from Freiheitsring (Frechen). 241 records from Planktic foraminifera abundance of Hole 67-499B. 1142 records from Range table from planktonic foraminifers in ODP Hole 154-925A. 30 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-913B. 57 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tityridae. 30659 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 3941 records from UAFMC Mammals. 52 records from Coleção de Ascidiacea do Museu Nacional - UFRJ. 2775 records from (Table T4) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1050C. 170 records from Thistles and numbers of observed invertebrates, fungi and damage types. 49 records from Additional records for Stenosagola newtoni Park & Carlton, 2013 (Staphylinidae: Pselaphinae: Faronitae), with notes on aedeagal morphology. 683 records from Lama Forest reserve Inventory, South Benin. Data published in the framework of JRS Benin project. 4303 records from Odonata Collection. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 372 records from Colección de Entomología - Arthropoda. 417946 records from Entomology, Natural History Museum, University of Oslo. 6103 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 31530 records from CAS Mammalogy (MAM). 11708 records from The Erysiphales Collection at the Botanische Staatssammlung München. 5 records from Analyses of the recent components of sediment core PS1400-4. 342 records from (Table A.10) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (150-500 µm). 592 records from Antarctic Krill occurrence data from Ukraine YUGNIRO Institute. 90 records from Schulhof Bühlschule Giengen. 2945 records from (Figure 4) Distribution of planktonic foraminifers in the Cenozoic sediments of DSDP Site 71-512. 1741 records from Benthic foraminifera abundance of Hole 84-570, Part 1. 73 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 13 records from Collection Reptilia fossil SMF. 2324 records from Eriophyoid Mites of Poland. 836971 records from Bernice P. Bishop Museum. 11591 records from (Table T6) Foraminifer distribution in ODP Hole 188-1167A sediments. 22116 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 1761 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 5733 records from Small Mammal Research Database. 56302 records from Kathryn Kalmbach Herbarium. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 48 records from Trockenrasen bei Dörndorf. 84 records from BIRDRACE Birding for Nature. 576 records from Distribution of agglutinated foraminifers in sediment core Well 6407/9-3. 94 records from Coccolith counts of multinet SO119_MSN1298. 19 records from Nannofossil abundance of Hole 31-298. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/107-5. 29 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 4 records from Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China. 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 1 records from Notizen über Oribatei (Acari). III. 2949 records from Algae, Specimens, Agder naturmuseum (KMN). 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 39385 records from SAEON: Historical Research Survey Database (1897-1949). 84521 records from BioGIS - Vascular plants - INPA database. 160 records from Wirbach-Taubental (Bad Blankenburg). 47 records from Schulgelände Ceciliengymnasium. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 103 records from BIRDRACE Die Otzberger. 186 records from Total foraminifera counts of multinet M21/1_MSN604. 45 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1385. 23 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5136-1. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_5-CTD56. 70 records from Parkuntersuchung Weißer See. 44 records from (Table 6) Distribution of nannofossils in DSDP Hole 87-583G. 1191 records from Relative abundance of Neogene nannofossils at ODP Site 138-850 from the eastern equatorial Pacific. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 8 records from Lathrolestes Förster, 1869 (Hymenoptera, Ichneumonidae) from Brazil, with description of two new species and a key to the Neotropical species. 8 records from New taxonomic, stratigraphic, and geographic information on the genus Faksephyllia Floris, 1972 (Scleractinia; Caryophylliidae); first records from the Oligocene of Austria, Germany, and Italy. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 482 records from Total foraminifera counts of multinet M6/7_MSN91. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 170 records from Scottish Natural Heritage - The occurrence and distribution of Najas flexilis (Slender naiad) in Loch of Craiglush, Loch of the Lowes and Loch of Butterstone. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 7 records from Abundance of nematoda in sediment profile M3/1_029 from the Iberian deep sea basin (Table 5). 6 records from Nannofossil abundance of Hole 7-63. 76 records from Coccoliths in sediment core PS1533-3. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 315 records from Planktic foraminifera counts of sediment core RC17-69. 30 records from Southern Ocean oligochaete occurrence data - a literature-based compilation. 227 records from (Table 6) Chemical composition of basalts from the Mid-Atlantic Ridge in the Doldrums Fault Zone. 708 records from Phytoplankton samples - 2005/06 V3 BROKE-West. 195 records from Total foraminifera counts from multinet M31/3_MSN923. 57 records from Nannofossil abundance in sediment core PS1311-4. 31 records from SNH Invertebrate Site Condition Monitoring 2013/14: Cadder Wilderness SSSI. 1551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 1028827 records from SEAMAP - marine mammals, birds and turtles. 54059 records from Pelagic Fish Observations 1968-1999. 154 records from Planktic foraminifera distribution of sediment core TRI171-27. 2 records from Occurrence of mammalia relicts at site Dechenhöhle. 778 records from Planktic foraminifera abundance of Hole 40-362. 318 records from Nematode abundance in cold seep sediments of the Darwin mud volcano. 4051 records from Homoptera. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 1853 records from Yeast Collection in BCRC. 19 records from Three new Scandinavian species of Culicoides (Culicoides): C. boyi sp. nov., C. selandicus sp. nov. and C. kalix sp. nov. (Diptera: Ceratopogonidae). 6062 records from Lichens of Knyszyn Forest. 1709819 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 106 records from Anfibios y reptiles de la sierra de Cuatro Venados, Oaxaca, México. 8858 records from (Appendix 2a) Foraminiferal analyses of research borehole Sonder Vium. 32 records from Billards A. 1936. Les fonds de peches pres d Alexandrie. VI Hydroidea. Notes et memoires No 24. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 74 records from SuLaMa reptile monitoring. 85 records from Plasm bearing foraminifera counts from M35/1_MSN1053. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 93 records from CCUG Microorganisms databases(Fungi). 48700 records from Museu Paraense Emilio Goeldi - Ophidia Collection. 17980 records from Impetus - Herbarium Hamburgense. 97 records from Schulgelände Regelschule Gorndorf/ Umgebung Jugend- und Stadtteilzentrum Gorndorf. 302 records from Stadtpark Sulzbach-Rosenberg. 168 records from Weidenhüttendorf an der Würm (München). 195 records from Occurrence of mammalia relicts at site Weinberghöhlen/Mauern. 1 records from Planktic foraminifera abundance of Hole 54-420A. 774 records from Planktic foraminifera abundance of Hole 80-549A. 1731 records from (Figure 3) Range of selected planktonic foraminifera in Paleocene samples of DSDP Hole 93-605. 862 records from (Appendix A4) Planktonic foraminifera of ODP Hole 172-1062B. 311 records from Avena wild species VIR Herbarium. N.I.Vavilov Institute of Plant Genetic Resources (VIR). 2 records from New data on the rare Afrotropical scarab beetles Orphnus drumonti Frolov and Delopleurus naviauxi Frolov et Cambefort (Coleoptera, Scarabaeidae, Orphninae and Scarabaeinae). 14 records from Two new species of Stenaelurillus Simon, 1886 from India (Araneae: Salticidae: Aelurillina). 43066 records from NEOTROPICMYXO. A database of Myxomycetes from the Neotropics. 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 536 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 4 records from First verified record of the ant genus Calyptomyrmex (Hymenoptera: Formicidae) from India, along with a revised key to known Indomalayan species. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 1541 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 109176 records from Herps Specimens. 32825 records from National fish tag database. 6 records from Sediment properties of core PLG93_BCORE1. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 57 records from Range table from planktonic foraminifers in ODP Hole 152-915A. 506 records from Range table from benthic foraminifers in ODP Hole 146-889A. 578 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 22 records from Cryptic diversity within the narrowly endemic Lerista wilkinsi group of north Queensland—two new species (Reptilia: Scincidae). 14 records from Clarification of Einfeldia Kieffer, 1922 (Diptera: Chironomidae) with E. australiensis (Freeman, 1961), comb. n. based on immature stages. 66 records from Mammals (KIEE-MM). 5549 records from Diplopoda (NSMK-DI). 1 records from Zetes cespitum. 1201 records from Monocotyledonous Geophytes of Fergana Valley. 597 records from Collection Crustacea - KAUMM. 5 records from Two new species of Diastatotropis Lacordaire (Coleoptera: Anthribidae) from east Madagascar with a key to species of the genus. 77 records from Inhaltsstoffe_Blattmischproben_2008. 49730 records from IMOS - AusCPR: Zooplankton Abundance. 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 107 records from BIRDRACE Herford Birders. 235 records from Total foraminifera counts from multinet M31/3_MSN905. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 65 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211670-7. 47 records from Université Pédagogique Nationale de Kinshasa (UPN) - Plantes fourragères de la République démocratique du Congo - Projet CABIN. 9 records from (Table 2) Macrobenthos on the floor of the West Bay of the Furugelm Island, Sea of Japan. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 46786 records from Bosque Mesófilo de Montaña de México. 1 records from Nothrus biverrucatus. 11 records from Biology and Ecology of Cryopelagic Amphipods from Arctic Sea Ice Collected near Franz Josef Land in the summer of 1994. 3947 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 588 records from Relative abundance of ostracods in sediment core Lz1120. 372 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 354 records from Relative abundance of planktonic foraminifera in sediment core L-66. 40 records from Schulwiese des Erich Kästner Gymnasiums (Laatzen). 25 records from Benthic foraminifera abundance of Hole 1-4. 210 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction > 20µm. 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 12 records from Spider hosts (Arachnida, Araneae) and wasp parasitoids (Insecta, Hymenoptera, Ichneumonidae, Ephialtini) matched using DNA barcodes. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, 63-125 µm fraction. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 26 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1368. 356 records from Biotope in Rheine - Aktion 350. 1729 records from Biodiversidad de Datura (Solanaceae) en México. 44 records from Flora und Fauna in unserer Kita. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-15-3. 331 records from Size of planktic foraminifera at CTD station PS55/082-1. 11 records from A new species of the catfish genus Akysis (Siluriformes: Akysidae) from southern Borneo.. 69 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 12 records from Abundance of radiolaria at station LV28-40-2. 1 records from Hausgarten. 14 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-115BX. 766 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 86194 records from West African Vegetation Database. 886 records from Lepidoptera Observations from New Zealand by Donald Hobern. 265 records from CNIN/Mantodea. 365 records from Bird Specimens of Miyazaki Prefecture Museum of Nature and History. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 9 records from Analyses of the recent components in the sand fraction of sediment core PS1217-1. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 12 records from Microplankton abundance at bottle station SEPT-1999-K9. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 9633 records from Coleção Entomológica do Depto. de Sistemática e Ecologia. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 24 records from Abundance and carbon biomass of phytoplankton at station TT007_7-CTD88. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 34586 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 17 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 14 records from Benthic macrofauna abundance of sediment core 12930-093. 86 records from Fliegenhaupt Marksuhl. 141 records from Fig. 7. Relative abundance of ostracod species in composite core JH05. 1130 records from Ostracoda in sediment core PS51/154-11. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 320 records from Myxomycetes collection of the University of Eastern Finland. 441 records from Pollen analysis of surface samples from Germany and Austria. 25471 records from Ibaraki Nature Museum, Arthropoda collection. 30985 records from MEXU/Asteraceae. 176 records from INSECT COLLECTION. 93 records from Südwestlich der Parkwiesen. 12 records from Abundance of microplankton from bottle APRIL-2000-K2. 107 records from Planktic foraminifera abundance of Hole 18-180. 99 records from Planktic foraminifera abundance of Hole 94-610E. 252 records from Range table from planktonic foraminifers in ODP Hole 155-934A. 16 records from Qualtitative analysis of calcareous dinocysts along profile Stevns-Klint. 254 records from Tage der Artenvielfalt rund um die Naturschutzstation Molsberg. 121 records from Dorset Argiope - NBN South West Pilot Project Case Studies. 365 records from Colección Herpetológica de la Patagonia. 306 records from (Table DR1) Biofacies, percentages of important benthic foraminifera and isotope data at ODP Site 758. 1368 records from Collection Crustacea ZMG. 1618 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during two Michael Sars cruises in 2000. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 1 records from Pollen and spore abundance of Hole 42-379A. 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 201 records from Mammals in MZNA-VERT: project CAS. 37 records from Study on Tychini of Balkan Peninsula (Coleoptera, Staphylinidae, Pselaphinae). 70 records from Tab. A6: Anzahl von M. balthica während der Ansiedlungszeit. 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 256 records from BIRDRACE Upupa epöpse. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 77 records from Total foraminifera counts from M35/1_MSN1075. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 2445 records from V. N. Karazin National University. 30 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 27 records from (Table 12) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-666A. 2723 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Cirolana00/5. 924 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 81 records from Range table from benthic foraminifers in ODP Hole 172-1061C. 164 records from Range table from benthic foraminifers in ODP Hole 192-1186A. 18 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 141-860B. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 8 records from UWYMV Herpetology Collection (Arctos). 6738 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 26 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 1294 records from Global Butterfly Information System (GloBIS). 228 records from Total foraminifera counts of multinet M36/6_MSN1193. 66 records from Foraminifera species abundances from tow TT007_10-MOC20. 9 records from Microzooplankton abundance and biomass at station TT043_9-1. 611 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Chavez 2011. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 24 records from (Table 7) Distribution of Pleistocene to Miocene nannofossils in ODP Hole 108-661A. 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 9728 records from Birds of Ireland. 7966 records from MfN - Phasmid Collection. 320 records from Planktic foraminifera assemblage in sediment core GIK11944-1. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-120BX. 107 records from 1st Austrian Birdrace (Wien). 2268 records from (Table 1) Distribution of Cretaceous-Tertiary benthic foraminifers in ODP Hole 129-802A. 2000 records from (Table A2) Sea surface temperature reconstruction of DSDP Site 94-607 in the North Atlantic. 208 records from Programa para la Conservación Integral de Diez Especies de Plantas Prioritarias del BST. 1 records from Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information. 2839 records from Rocky Shore Macroalgae. 422 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 81 records from Review of the leafhopper tribe Stenometopiini (Hemiptera: Cicadellidae: Deltocephalinae) from China with description of four new species. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 2880 records from Coleoptera, NEF. 10 records from Plateurytion roigi sp. nov., a new geophilid centipede (Myriapoda: Chilopoda: Geophilomorpha) from Southern Chile. 2 records from A New Species from Mountain Forest Soils in Japan: Porosia paracarinata sp. nov., and Taxonomic Concept of the Genus Porosia Jung, 1942. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 1 records from Opamyrma hungvuong, a new genus and species of ant related to Apomyrma (Hymenoptera: Formicidae: Amblyoponinae). 337 records from Abundance of calcareous dinocyst along profile Calais-Escalles. 1271 records from Distribution of planktonic foraminifera of sediment core Core190. 3978 records from Colección de Entomopatógenos de México (CNRCB). 2 records from The second species of Phanoperla (Plecoptera: Perlidae) from China, P. hainana sp. nov., from Hainan Island. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 145 records from privater Garten. 46 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Caprimulgidae. 14 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/042-2. 243 records from (Table 3) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-749B. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 9 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 6199 records from SANBI: DNA Banking(1987-2011). 781 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 122 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1359. 343 records from Collection Cnidaria - ZMB. 2088 records from Benthic foraminifera of sediment core MD99-2286. 718 records from Zukünftiges NSG Höftland/Bockholmwik. 117 records from Muskox Abundance. 1042 records from Planktic foraminifera abundance of Hole 37-333. 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 12768 records from (Table 4) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-872C. 127 records from Collection Hydrozoa - ZMB. 1312 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 12 records from Abundance of radiolaria at station LV28-44-1. 524 records from (Table 2) Benthic foraminiferal composition at University of Texas Marine Science Institute (UTMSI) piston cores at Costa Rican slope sediments. 177 records from Donauinsel des BN bei Entau. 50 records from Laubmischwald bei der Internationalen Grundschule Potsdam. 6 records from Nannofossil abundance of Hole 55-430B. 144 records from BIRDRACE Punkbirder Helgoland. 3 records from Antarctic Arrow worms. 2 records from Nothrus palustris. 679 records from Results of palynological analysis of Hole 302-M0004A. 2402 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 92 records from Range table from planktonic foraminifers in ODP Hole 167-1017B. 91 records from Benthic foraminifera abundance of Hole 84-569A. 2306 records from (Table T4, T5, T6, T7) Percentage of agglutinated and calcareous benthic foraminiferal species in ODP Hole 178-1098C. 19557 records from Collection Thysanoptera SMF. 7938 records from Hymenoptera collection, Natural History Museum, University of Oslo. 2079 records from (Table 1) Occurrence and frequency of benthic foraminifera in Paleocene samples of DSDP Hole 93-605. 3 records from New species of Myrmicine ants from Western Australia (Hymenoptera: Formicidae). 492 records from Verneplan Hjerkinn karplanter. 3710 records from Araneae_Raw1. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 3 records from Mammalia (SMNH-MM). 2 records from A new species of Prohatschekia Nunes-Ruivo, 1954 (Siphonostomatoida: Hatschekiidae) from the scorpaenid fish, Scorpaena neglecta Temminck & Schlegel, 1843 (Scorpaeniformes: Scorpaenidae), in Korean waters. 6 records from New records of Indian Nematomorpha, with the description of a new species from the genus Chordodes. 279 records from Planktic foraminifera abundance of Hole 11-98. 68 records from Range table from benthic foraminifers in ODP Hole 144-873B. 13646 records from Senckenberg - CeDAMar Resource. 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 5 records from Colección de Referencia de Reptiles del Museo de Ciencias de la Universidad El Bosque. 12 records from Laccomimus xikrin sp. nov. and new records of other species of Laccomimus Toledo & Michat, 2015 (Coleoptera: Dytiscidae: Laccophilinae) from Brazil. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 19100 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 1 records from Erysipelothrix inopinata sp. nov., isolated in the course of sterile filtration of vegetable peptone broth, and description of Erysipelotrichaceae fam. nov.. 2 records from Dinámica poblacional de Mammillaria crucigera y Neobuxbaumia macrocephala en la región de Tehuacán-Cuicatlán. 1826 records from Collection des Mollusques (BOUM). 49637 records from Monitoring data from the federal state Hesse (Germany). 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 57 records from Garten in Schmölln. 18 records from Landschaftsschutzgebiet Buchhorst2. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 102 records from Foraminifera species abundances from tow TT011_11-MOC72. 28934 records from Coleção de Abelhas do Museu de Ciências e Tecnologia da PUCRS. 483 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 216 records from Monitoreo biológico en la cuenca Dagua - Subcuenca La Guinea ARA - RARE - CVC – Asociación Calidris. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 7427 records from Weevils of the Tatra Mts.. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 156 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 31 records from Coleção de Nemertea do Museu Nacional - UFRJ. 5 records from Streuobstwiese (Mittelgasse 4). 214 records from Binsenwiesen. 347 records from (Table 4) Standing stock values of important species in surface sediments. 36 records from Stable isotopes measured on Ammonia beccarii from sediment core GIK12594-2. 28 records from Seasearch Crawfish, Palinurus elephas, Surveys. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 18 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5120-2. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 11 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 24 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 8 records from A review of the genus Spiropagurus Stimpson, 1858 (Crustacea: Decapoda: Paguridae) from the China seas. 6394 records from HCDAL - Herbário Caririense Dárdano de Andrade-Lima. 139 records from Revision of the myrmicine ants of the Adelomyrmex genus-group (Hymenoptera: Formicidae).. 1 records from Celaeno spinosa. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 16 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 961 records from Fish monitoring data in Lake Kasumigaura. 4 records from Estimated plankton abundance at station PS63/064-6. 14 records from Occurrence of mammalia relicts at site Crumstadt 1. 8 records from Pollen and spore abundance of Hole 42-380. 300 records from Gunma Museum of Natural History, Fish Specimen. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 20847 records from Coleção Ictiológica (MNRJ), Museu Nacional (MN), Universidade Federal do Rio de Janeiro(UFRJ). 1952 records from ISM Ichthyology Collection. 193 records from Total foraminifera counts of multinet M21/3_MSN663. 44 records from Total foraminifera counts of multinet M21/4_MSN721. 141 records from Plasm bearing foraminifera counts of multinet M21/1_MSN604. 276 records from Planktic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 208 records from Black flies (Diptera: Simuliidae) of Turkish Thrace, with a new record for Turkey. 15 records from Diatom abundance measured on water bottle samples at station PS58/009-2. 6 records from Cobitis nalbanti, a new species of spined loach from South Korea, and redescription of Cobitis lutheri (Teleostei: Cobitidae). 153 records from Selztal bei Friesenheim. 87 records from Klütwald. 89 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction 63-150 µm. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 25 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_8-CTD93. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 5 records from Distribution of meiobenthos in sediment core M19_201-2 of the northeastern Atlantic (Table 1). 8649 records from Fossil (WSHN-FO). 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 316 records from (Table 2) Distribution of planktonic foraminiferal tests in sediments from Core ML7_475. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 2784 records from (Figure 3) Distribution of benthic foraminifers in the Albian of DSDP Hole 71-511. 20973 records from Real Jardin Botanico, Madrid: MA-Funhist. 1 records from Range table from planktonic foraminifers in ODP Hole 174-1072A. 11 records from Range table from planktonic foraminifers in ODP Hole 178-1096C. 764 records from BioGIS - Fish - INPA database. 11268 records from Aphidoidea Collection. 13 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en Laguna Las Barrancas (Spitznagel, octubre 1999). 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 33 records from Astyanax endy (Characiformes: Characidae), a new fish species from the upper Río Bermejo basin, northwestern Argentina.. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 45 records from Nannofossil abundance of Hole 28-265. 21 records from Meiofauna abundance in sediment core 13077-006. 12 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-131BX. 1215 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 2970 records from (Table 2) Distribution of planktonic foraminifera in the latest Oligocene to Holocene section of ODP Hole 149-897C. 154124 records from Arizona State University Lichen Collection. 96 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 578 records from (Figure 2c) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3239. 1 records from Damaeus auritus. 22 records from Synonymy of Homalopoltys (Araneae: Araneidae) with the genus Dolichognatha (Araneae: Tetragnathidae) and descriptions of two new species. 12 records from The genus Dromanthomorphus Pic, 1921 (Coleoptera, Cleroidea: Malachiidae) in South-East Asia. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 145 records from Phytoplankton abundance at station CD46_0405C#7. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 27828 records from svalbardflora.no. 6 records from Planktic foraminifera abundance of Hole 23-226. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 42 records from Was singt im Duvenstedter Brook. Wir zählen die Brutvögel im Naturschutzgebiet. 41460 records from Herbarium (UNA). 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 57 records from Occurrence of mammalia relicts at site Moladova V. 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 1 records from Planktic foraminifera abundance of Hole 8-73. 3 records from Range table from planktonic foraminifers in ODP Hole 183-1141A. 246 records from Benthic foraminifera abundance of Hole 73-524. 131 records from Range table from benthic foraminifers in ODP Hole 189-1172A. 5 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 6987 records from National Trust - Ickworth species data held by The National Trust.. 6422 records from Ájtte. 5 records from Rediscovery and redescription of Centrodora damoni (Girault) (Hymenoptera: Aphelinidae) from Australia, an egg parasitoid of Gonipterus spp (Coleoptera: Curculionidae), after nearly a century. 233 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 1563 records from Mid Ulster Hare Surveys 2012-2015. 130 records from Endemic earthworms (Oligochaeta: Lumbricidae) of the Balkan Peninsula: a review. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 47499 records from Sphaeroceridae Collection. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1 records from Flora of Suriname, volume VI, part I. 144765 records from Invertebrates Collection of the Swedish Museum of Natural History. 114 records from BIRDRACE Di-Bi-Di-Birder. 36613 records from Inventaire National du Patrimoine Naturel : Amphibiens et Reptiles de France (Enquête 1). 5042 records from Tracheophyta collection of Biodiversity Center of Japan, Ministry of Environment. 193390 records from Mycology herbarium, Oslo (O). 5 records from Aretidris, a new genus of ants (Hymenoptera: Formicidae: Myrmicinae) from the mountains of Luzon Island, Philippines. 1165 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 30129 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 8 records from Krittenhorster Wald (Ostkilver). 74 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core GIK23059-2. 3 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 16 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 7 records from Pseudomystus stenogrammus, a new species of bagrid catfish from Borneo (Teleostei, Bagridae).. 18026 records from Herbario micológico de La Universidad de La Laguna, Tenerife: TFC_Mic. 180 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres en La Chinantla. 2 records from Nannofossil abundance of Hole 6-49. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 1295 records from Planktic foraminifera counts of sediment core RC08-49. 921 records from Planktic foraminifera counts of sediment core RC14-37. 1530 records from (Appendix B) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747C. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 189408 records from NINA insect database. 426 records from Myriapoda - SMF. 10 records from A new species of Neparholaspis (Acari: Parholaspididae) from Russia, with additional information on Neparholaspis evansi Krantz, 1960. 177 records from (Table 11) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-589. 10567 records from Coleoptera collection of National Museum of Nature and Science. 82 records from Countryside Council for Wales - Non-native species records from Countryside Council for Wales (CCW) non-native monitoring research and ad-hoc sightings. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 1680 records from Avifauna del Altiplano de San Luis Potosí. 14 records from Nannofossil abundance of Hole 85-573. 13865 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF-Lich. 190 records from Foraminifera abundance of sediment core MD81-LC07. 3 records from Analyses of the recent components of sediment core PS1215-2. 66 records from Occurrence of mammalia relicts at site Malerfels_I. 120 records from Fiocruz/CYP - Coleção de Yersinia pestis. 692 records from Planktic foraminifera abundance of Hole 40-360. 3 records from Range table from planktonic foraminifers in ODP Hole 171-1049C. 1269 records from Distribution of benthic foraminifers (living) in surface sediments (Table 4). 1042 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 190 records from ENBI-Dataset of GART-GloBIS. 8237 records from Naturalis National Natural History Museum (NL) – Pisces_Cichlidae of Lake Victoria. 1 records from A new macropterous species of a rarely collected subfamily (Heteroptera, Tingidae, Vianaidinae). 13733 records from Collection Bryozoa SMF. 50 records from Plasm bearing foraminifera counts from M35/1_MSN1047. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 144 records from Planktic foraminifera of surface sediments off Portugal and Morocco (Table 4). 2 records from Microzooplankton abundance and biomass at station TT050_19-3. 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 30008 records from Lepidoptera specimen database of Japan. 129 records from Benthic macrofauna abundance of subcores of sediment core 12930-084. 3982 records from Plant (GFEI-PL). 262 records from (Appendix 6) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD95-2041. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 55 records from (Table 2c) Species compositioon of planktonic foraminiferas in bottom sediments from Core ML1_66. 18894 records from (Table 5) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Site 114-702. 86 records from Pollen analysis of sediment core GIK16856-2. 2483 records from Bacteria collection of National Institute of Public Health, Poland. 193 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-86. 189 records from (Table A.09) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (125-250 µm). 269 records from 3. Tag der Artenvielfalt Hockenheim. 76 records from Occurrence of mammalia relicts at site Vindija. 9 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-7. 296 records from DJH. 141 records from Schulhof und Anlagensee in Nellingen. 20 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 53 records from Occurrence of mammalia relicts at site Roter Berg bei Saalfeld. 2346 records from (Fig. 8) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 44-391C in the North Atlantic. 15 records from Discontinuous color variation in the assassin bug species Tiarodes miyamotoi (Hemiptera: Reduviidae: Reduviinae). 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 27 records from Zwickau- Schwanenteich. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 1 records from Arthropoden aus südostalpinen Höhlen.. 10 records from Phytoplankton abundance at station Rigel_6_2005-02 in Febraury 2005, Chipana, Chile. 34 records from Urolophus kapalensis sp. nov., a new stingaree (Myliobatiformes: Urolophidae) off eastern Australia.. 10000 records from Vascular Plant Collection of Natural History Museum and Institute, Chiba. 14219 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 668 records from Naturschutzgebiet Sistig-Krekeler-Heide. 94 records from Planktic foraminifera abundance of Hole 80-550. 1 records from Abundance of benthos infauna at station GIK23004-3. 72636 records from Insect Collection of Taiwan Forestry Research Institute. 554 records from SNH Invertebrate Site Condition Monitoring 2013/14: Abernethy Forest SSSI. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 314 records from (Appendix 1a) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber in the Holocene section of sediment core GeoTu_SL096. 2713 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 15 records from Spiders of the genus Habrocestoides from China (Araneae: Salticidae). 55 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2008. 127 records from Range table from planktonic foraminifers in ODP Hole 171-1053B. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1100C. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 11 records from Observation of birds at station PS14/156 along 49° West. 599 records from NHT flora. 212 records from (Table T4) Planktonic foraminifera abundance of ODP Site 170-1042 sediments. 84800 records from UPCB - Herbário do Departamento de Botânica. 5398836 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 677 records from Meiofauna abundance of central Mediterranean Sea mud volcano sediments. 39684 records from MSB Bird Collection (Arctos). 142 records from Tejidos de quirópteros de tres localidades del caribe colombiano. 50 records from Lindesnes. 767 records from BioGIS - Bats - Asaf Tsoar database. 10168 records from Estudios bióticos: Plantas, edafofauna epígea, anfibios y aves en el complejo de páramos Cruz Verde - Sumapaz. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 356 records from Morphologische Daten von Puffinus creatopus. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 29002 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. 1212 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 39 records from Mineralogy of serpentine muds of ODP Leg 125 holes (Table 1). 1154 records from Collection Plecoptera - SMF. 313162 records from Observational database of Icelandic plants. 11300 records from Eastern Canada Benthic Macro Fauna (OBIS Canada). 1023 records from Spencer Entomological Museum. 9031 records from Herbario Kew del Real Jardín Botánico (RBGKEW). 2148 records from Eppingen und Umgebung. 1139 records from Phytoplankton abundance in surface water in September 1996, Ilo, Peru. 1626 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1119. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 2182 records from Avifauna de la Reserva de la Biosfera La Sepultura, Chiapas. 55 records from Two new species of the scorpionfish genus Trachyscorpia (Sebastidae: Sebastolobinae) from the southern Indo-West Pacific, with comments on the distribution of T. eschmeyeri.. 3 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 5205 records from Botanical Garden Collection. 456 records from Range table from benthic foraminifers in ODP Hole 144-873A. 3952 records from Range table from benthic foraminifers in ODP Hole 159-962D. 43 records from Bryconops magoi and Bryconops collettei (Characiformes: Characidae), two new freshwater fish species from Venezuela, with comments on B. caudomaculatus (Gunther).. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Pelops phaeonotus. 1 records from Diatom abundance of Hole 95-613. 2 records from Parvimyrma gen. nov. belonging to the Solenopsis genus group Hymenoptera: Formicidae: Myrmicinae: Solenopsidini).. 1 records from Oribates mollicomus. 2114 records from Dry Tortugas Reef Visual Census 2010. 2 records from Two new species of the genus Deontolaimus de Man, 1880 (Nematoda: Leptolaimidae) from mangrove ecosystems of Vietnam. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 5103 records from Elaboración del banco de datos de las colecciones del Museo de Zoología-CIQRO. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 81329 records from natagora-earlybirds. 820552 records from Fauna Atlas N.T.. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 17943 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 12 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 163 records from Tiere und Pflanzen am Pfannenbach. 30 records from Leben auf einer Sturmfläche. 87 records from Total foraminifera counts of trap L2_92_B49. 1374 records from A nest-site survey of Barn swallow at railroad stations in the Kinki District,south-central Japan. 2916 records from Orthoptera (Grasshoppers & Crickets) & allied insects of Ireland. 92 records from Plasm bearing foraminifera counts of multinet M26/1_MSN843. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-19-2. 5 records from Tuttlinger Tag der Artenvielfalt. 316 records from Planktic foraminifera counts of sediment core V14-101. 1393 records from Lepidoptera from Rancho Grande, Rondônia, Brasil. 13 records from Description of lithologic section units of IODP Hole 325-M0031A. 501 records from Planktic foraminifera assemblage in sediment core SU90-I03. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 73 records from Planktic foraminifera abundance of Hole 2-11. 2034 records from Herbarium of Namur. 878 records from Planktic foraminifera abundance of Hole 84-568. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 56 records from Range table from planktonic foraminifers in ODP Hole 167-1010C. 1512 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 923 records from Collection Graptolithina fossil SMF. 1 records from The Oribatid Family Phthiracaridae I. Introduction and Redescription of Hoplophthiracarus pavidus (Berlese). 1322 records from Targeting a portion of central European spider diversity for permanent preservation. 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 4 records from Arthropoden aus südostalpinen Höhlen.. 18 records from Variación genética del manatí (Trichechus manatus), en el sureste de México y monitoreo con radio-transmisores en Quintana Roo. 3621 records from Millenium Seedbank (MSB). 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 159 records from Plasm bearing foraminifera counts of multinet M21/1_MSN606. 137 records from Abundance of planktic foraminifera at CTD station PS55/077-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-06-4. 4 records from Nannofossil abundance of Hole 29-281A. 39033 records from SBMNH Vertebrate Zoology. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 95 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 70 records from Planktic foraminifera abundance of Hole 84-569A. 46 records from Coleção de Brachiopoda do Museu Nacional - UFRJ. 3172 records from ZUEC-COL - Coleção de Coleoptera do Museu de Zoologia da UNICAMP. 50834 records from Institute of Dendrology PAS, Flora of Sudety Mountains. 9499 records from Sightings Map of Invasive Plants in Portugal. 86556 records from NINA Vanndata øvrige arter. 31 records from Further contribution to the knowledge of Georgian species of the Carabus Linnaeus, 1758 subgenus Neoplectes Reitter, 1885, with description of a new subspecies of C. titarenkoi Zamotajlov & Fominykh, 2014 (Coleoptera: Carabidae: Carabini). 4900 records from Actualización de la colección ictiológica de Ecosur-Chetumal. 99 records from Düne am Ulvenberg (Darmstadt). 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-12-1. 26 records from Ostracoda abundance of Hole 13-132. 68 records from Macrofauna abundance in surface sediment sampled during cruise DI229. 133 records from Catalogue of type specimens of fungi and lichens deposited in the Herbarium of the University of Granada (Spain). 1547 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 610 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 785 records from Faunal distribution of the most important planktic foraminiferal species in the investigated surface sediment samples from the Chilean continental slope between 23°S and 44°S. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 56317 records from Fish Specimens. 11 records from Nannofossil abundance of Hole 6-56B. 28 records from Nannofossil abundance of Hole 26-253. 18 records from Meiofauna abundance in sediment core 13200-012. 615 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part I. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 18 records from Planktic foraminifera abundance of Hole 32-310. 759 records from Planktic foraminifera abundance of Hole 47-398D. 15 records from Range table from planktonic foraminifers in ODP Hole 169-1036A. 32 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 208 records from Thistles damage. 7 records from Additions to the myxobiota of the Åland Islands. 350140 records from TPWD HARC Texas Coastal Fisheries Aransas Bay Trawl. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 39 records from A review of the Malagasy Pachypanchax (Teleostei: Cyprinodontiformes, Aplocheilidae), with descriptions of four new species.. 26464 records from Marie-Victorin Herbarium (MT) - Bryophytes. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 166 records from Simpson´s diversity of Coleoptera and Heteroptera. 20 records from Motzener Tonsee. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 2 records from An extraordinary new genus and species of spider wasps (Insecta: Hymenoptera: Pompilidae) from Southeast Asia. 16 records from Dinoflagellate cysts of surface sediments. 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 11981 records from SMNK Mantid Collection. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 190 records from Colección Paleontológica Invertebrados e Icnologia - CONICET- Argentina. 1251 records from Visual Plants (144.41.33.158) - Herbarium specimen from "EA", Kenya. 31 records from Planktic foraminifera assemblage in sediment core GIK17732-1. 1346 records from Percentages of planktonic foraminifera species in sediment core V25-59. 260 records from Range table from planktonic foraminifers in ODP Hole 155-930D. 226 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-959D. 55 records from Three new species of Ametadoria Townsend (Diptera: Tachinidae) from Area de Conservación Guanacaste, Costa Rica. 281250 records from Quadrige. 187 records from Taxonomic revision of the Pachycondyla apicalis species complex (Hymenoptera: Formicidae).. 4 records from A new species of the genus Paramesotriton (Caudata: Salamandridae) from Fujian, southeastern China. 13 records from Tag der Artenvielfalt am Bruckenwasen. 161 records from BIRDRACE Nord-Seh-Team. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 82 records from Fiocruz/CLEP - Coleção de Leptospira. 60000 records from Birds (NSMK-BI). 5 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 7 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 143763 records from University of British Columbia Herbarium (UBC) - Algae Collection. 92 records from Siliceous microfossil occurrence, Site 177-1094. 940 records from Benthic foraminifera abundance of Hole 84-570, Part 2. 227 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1051 records from Field Study Group of the Dutch Mammal Society (NL) - 2003 - Mammal Survey Alvao Natural Park, Portugal. 1863 records from Cowan Tetrapod Collection - Herpetology. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 2653 records from Florida Keys Reef Visual Census 2005. 89 records from Total foraminifera counts from multinet SO119_MSN1303. 706 records from (Table 1) Benthic foraminifera at DSDP Site 72-516. 4 records from Microzooplankton abundance and biomass at station TT054_24-21. 4054 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 3015 records from Bird specimens in Gifu Prefectural Museum. 3651 records from Planktic foraminifera abundance of Hole 72-516F. 389 records from Inventaire National du Patrimoine Naturel : CBN Bailleul. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 61 records from Taxonomic review of the genus Parastenolechia Kanazawa (Lepidoptera, Gelechiidae, Litini) from Mainland China, with descriptions of six new species. 25128 records from rmca-albertine-rift-butterflies. 244 records from WildesMoor bei Schwabstedt. 115 records from Plasm bearing foraminifera counts of multinet M21/1_MSN614. 144 records from Total foraminifera counts of multinet M21/2_MSN640. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 1 records from Microplankton counts and carbon biomass at station TT007_15-CTD160. 3 records from Nannofossil abundance of Hole 51-417D. 18 records from (Table 1) Early Miocene and late Oligocene ostracods in sediment core CRP-2A. 25372 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1379 records from Organic-walled dinoflagellate cyst counts of sediment core GeoB9503-5. 161 records from (Table 3) Palynomorph concentrations for ODP Site 105-645. 988 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 156 records from Levantamento da vegetação arbustiva do Parque Nacional do Jaú. 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 91 records from CNIN/Tipos Homoptera. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 1432 records from Quaternary benthic foraminifera abundance of Hole 95-612. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 82 records from Foraminifera species abundances from tow TT011_5-MOC63. 24 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD11. 28 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 189-1171D. 143 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 221 records from Table 1. Species richness and abundance of the benthic infauna of the North Sea, 1980-1985. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 8 records from Occurrence of mammalia relicts at site Grotte du Prince. 6264 records from (Table 2) Planktic foraminiferal abundance in Eocene to Oligocene sediments of ODP Hole 177-1090B on the Agulhas Ridge, South Atlantic. 45 records from Parcela Permanente en el Pantano Martos. 569 records from (Appendix D) Benthic foraminifera extinction group species in DSDP Hole 94-608. 9062 records from Northern Biodiversity Program Coleoptera (2010-2011). 27264 records from Formidabel; Belgian Ants Database. 75 records from (Table S2b) Nannofossil species richness in the Wilson Lake section. 24 records from New distributional data on ascidian fauna (Tunicata: Ascidiacea) from Mandapam coast, Gulf of Mannar, India. 2 records from A second species, and first Central American record, of the phorid fly genus Lenkoa Borgmeier (Diptera: Phoridae). 282 records from CSIRO, Cruise SS199402, Marine Biological Survey, Southeast Australia, 1994. 1380 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 126-790. 63 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_INSECTA. 56051 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 11 records from Occurrence of mammalia relicts at site Nörre-Lyngby. 264743 records from ArtenFinder. 1078 records from Fishes of the Congo River 2010 Expedition. 4188 records from Las monocotiledóneas mexicanas, una sinopsis florística. Parte II. 609 records from Countryside Council for Wales - Bat Roosts Database- South Wales. 1030627 records from Phanerogamic Botanical Collections (S). 810 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 14 records from A new subterranean Iberian Cephennium with unusually modified metatrochanters (Coleoptera, Staphylinidae, Scydmaeninae). 160 records from Total foraminifera counts of multinet M21/2_MSN658. 2 records from A new species of the genus Asthenara Förster, 1869 (Hymenoptera, Ichneumonidae) from Mexico with identification key. 71 records from (Table 3d) Distribution of planktonic foraminiferal tests in sediments from Core NKA-4T. 922 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 15016 records from iziko South African Museum - Fish Collection (AfrOBIS). 588 records from Distribution ashore and breeding places of southern elephant seals. 155 records from Bergbaufolgelandschaft am Muldestausee. 131 records from Artenvielfalt auf dem Schulgelände. 124 records from Occurrence of mammalia relicts at site Euerwanger Bühl. 535 records from Benthic foraminifera abundance of Hole 73-522. 69622 records from Fundación Miguel Lillo - Colección Entomológica. 7 records from A new Eastern Central Atlantic skate Raja parva sp. nov. (Rajoidei: Rajidae) belonging to the Raja miraletus species complex. 225385 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 382418 records from University of Florida Vertebrate Paleontology. 464 records from Lepidoptera systematic collection, NTNU University Museum. 852 records from flower availability 2008 Hainich. 9948 records from Bees of Canada / Gschwendtner property collection. 1965 records from Global caridean shrimp fauna. 54 records from Wiese am Unterbecken. 2 records from New distribution records for the rare genus Afrotremex Pasteels (Siricidae: Hymenoptera) and provision of interactive Lucid identification keys to species. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 84 records from BIRDRACE Vogelscheuchen. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 90 records from Total foraminifera counts of multinet PO231/3_MSN1332. 3 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B2_820-4. 8 records from Microzooplankton abundance and biomass at station TT045_29-1. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_5-CTD51. 23 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/042-2. 12 records from Distribution of meiobenthos in sediment core M23_134 of the northeastern Atlantic (Table 1). 6 records from Ökosysteme rund um Wedel. 2 records from Smear slide analysis of sediment core GeoB7427-2. 2 records from Nannofossil abundance of Hole 74-526. 3734 records from Anfibios, reptiles y mamíferos del corredor biológico del norte de Yucatán depositados en las colecciones de la Escuela Nacional de Ciencias Biológicas. 102 records from Ostracod abundance in sediment core Lz1120. 1000 records from Diplopoda (JJHA-DI). 27 records from New records of Sylvicola (Diptera: Anisopodidae) from Romania. 72 records from Plasm bearing foraminifera counts of multinet M21/1_MSN603. 33 records from Foraminifera species abundances from tow TT007_2-MOC4. 753 records from Dinoflagellates (organic) in surface sediments of the South Atlantic. 6 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 48 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 8 records from Abundance of radiolaria at station LV28-29-1. 36845 records from MfN - Fossil invertebrates Ia. 66 records from Range table from ostracoda in ODP Hole 151-910D. 104 records from Ross Sea Pycnogonids. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-097BX. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 741 records from Planktic foraminifera abundance of Hole 20-200. 465 records from Range table from planktonic foraminifers in ODP Hole 159-959A. 103 records from Catalogue of snout mites (Acariformes: Bdellidae) of the world. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1 records from Nouvelles fourmis de l'Imerina oriental (Moramanga etc.).. 11 records from Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan.. 9123 records from Flora of Słowiński National Park, Poland. 13968 records from NYSM Birds. 5429 records from Ibaraki Nature Museum, Algae collection. 61 records from The water mite family Aturidae Thor (Acari: Hydrachnidia) from Ghana, with the description of twelve new species. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 42619 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 16 records from Nannofossil abundance of Hole 47-398B. 29 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 17 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE258. 577 records from Marine Benthic Fauna List, Island of Læsø, Denmark. 34506 records from Herbarium de Geo. B. Hinton, México. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 366 records from Marine fauna survey of the Vestfold Hills and Rauer Island, 1981-82. 75 records from Range table from nannofossils in ODP Hole 199-1220A. 6801 records from UPRM Invertebrate Collection. 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 65535 records from OAC-BIO Herbarium. 17 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/011-3. 777 records from Planktic foraminifera counts of sediment core RC17-108. 1 records from Antarctic Marine Amoebae. 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 115 records from Range table from planktonic foraminifers in ODP Hole 155-931C. 2387 records from The French Collection of Medicago truncatula. 147 records from NABU-Auerochsenweide. 68 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-04. 5 records from Phytoplankton abundance at station Rigel_5_2005-07 in July 2005, Chipana, Chile. 855 records from (Table T7) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones Palpha-P3b. 26375 records from Provincial Museum of Alberta, Edmonton, AB, Canada. Birds (Aves). 535 records from Percentages of planktonic foraminifera species in sediment core V30-41. 994 records from (Table 6) Quaternary planktonic foraminifers at DSDP Site 65-483. 93712 records from Herbarium of Umeå University (UME). 27 records from Benthic foraminifera abundance of Hole 34-320A. 302 records from Range table from benthic foraminifers in ODP Hole 144-874B. 612 records from Range table from benthic foraminifers in ODP Hole 149-900A. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 585 records from (Tab. 4) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 11-105, Bahama Lower Continental Rise Hills. 264 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 195 records from Phytoplankton abundance in surface water in May 1997, Callao, Peru. 14 records from Collection Pantopoda SMF. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 2117 records from National Trust - Anglesey Abbey wildlife species data held by The National Trust.. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 3504 records from Alterra (NL) - Entomofauna inventory in Amerongen forest. 1 records from Arthropoden aus südostalpinen Höhlen.. 5116 records from Caracterización de la avifauna de las cuencas de los Ríos Cañas (Dibulla–Guajira), Garupal (Valledupar–Cesar), Arroyo Grande (San Juan de Nepomuceno–Bolívar), Aipe (Huila), Yaví (Tolima), Dagua (Valle del Cauca) como insumo para la identificación de oportunidades de conservación y de recuperación de servicios ecosistémicos del bosque seco.. 342 records from Distribution of planktonic foraminifera in sediment core R657 east of New zealand. 8 records from Occurrence of mammalia relicts at site Wretton. 2129 records from RBspirit - Rio de Janeiro Botanical Garden fluid-preserved specimens.. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 1000 records from Plant (KOBG_PL). 148 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE293. 520 records from Planktic foraminifera abundance of Hole 39-357. 102 records from Benthic foraminifera abundance of Hole 42-372. 1 records from Abundance of benthos infauna at station GIK23062-2. 1 records from On the Chilopoda from Turkey. 681 records from (Appendix) Planktonic foraminiferal abundances in ODP Hole 130-805C. 7056 records from EAN - Herbário Jaime Coelho de Moraes. 41 records from Revision and phylogeny of the Caribbean weevil genus Apotomoderes Dejean, 1834 (Coleoptera, Curculionidae, Entiminae). 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 2 records from Porifera ZMK. 96 records from Birdrace-federleser-Herford. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 438 records from (Table 4) Stratigraphic ranges of selected Oligocene planktonic foraminifers in ODP Hole 115-709A. 294 records from Naturgarten Langenholtensen. 2166 records from Prime Hoverfly (Insecta: Diptera: Syrphidae) Areas (PHA) as a conservation tool in Serbia. 498 records from Dinoflagellate abundance of Hole 94-611C. 1147 records from Herpetofauna de la región El Huizache, San Luis Potosí. 727 records from Range table from benthic foraminifers in ODP Hole 161-975B. 47289 records from Naturalis Biodiversity Center (NL) - Porifera. 1474 records from Estudios bióticos: Plantas, anfibios, aves y edafofauna epígea en el complejo de páramo Los Picachos. 21 records from Hungarosoma bokori Verhoeff, 1928 (Diplopoda: Chordeumatida): new insights into its taxonomy, systematics, molecular genetics, biogeography and ecology. 1 records from Emesopsis infenestra Tatarnic, Wall & Cassis, 2011 (Heteroptera: Reduviidae), genus and species new to New Zealand. 1 records from Beiträge zur Kenntnis paläarktischer Myriopoden. XI. Aufsatz: Neue und wenig bekannte Lithobiiden. 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 2 records from Discovery of a new millipede species in northern Vietnam, and the proposal of a new genus, Parariukiaria (Diplopoda, Polydesmida, Xystodesmidae). 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 112 records from BIRDRACE Gütersloher Gimpel. 57 records from Schulgarten Janusz-Korczak-Realschule. 58 records from Plasm bearing foraminifera counts of multinet M12/3_MSN560. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 300 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part II. 1833 records from DSMZ Fungi. 11370 records from Distribution of planktic foraminifers of core V22-174. 52 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 24 records from Occurrence of mammalia relicts at site Overmere. 44 records from Planktic foraminifera abundance of Hole 19-188. 2083 records from Planktic foraminifera abundance of Hole 72-517. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 67 records from Tongrube bei Hettstedt. 73544 records from Marsh Monitoring Program - Birds. 19 records from Dinoflagellate abundance of Hole 81-553A. 209 records from pflanzendiversitaet_2008_sch_zweiter_durchgang. 1 records from On the genus Sunius Curtis, 1829 of Turkey. IV. A new micropterous species from southwestern Anatolia and additional records (Coleoptera: Staphylinidae: Paederinae). 51 records from Total foraminifera counts of multinet M21/4_MSN712. 77 records from Total foraminifera counts of multinet PO231/3_MSN1330. 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 2050 records from Birds (ENHM-BI). 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 1998 records from Aves de la cuenca media del río Bogotá. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_2-CTD1. 78 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1b. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 753 records from Planktic foraminifera counts of sediment core V28-127. 484 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 117-726A. 20 records from (Table 2c) Nannofossil distribution chart of ODP Hole 122-762C. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 6627 records from ATCC Fungi Collection Catalog. 527 records from Inventaire floristique de Beza Mahafaly. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 241 records from BIRDRACE RennVögel Münsterland. 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 104 records from Total foraminifera counts of multinet M21/6_MSN778. 70 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1387. 57 records from Upper Aptian Serre Chaitieu (Niveau Fallot) G. ferreolensis and G. blowi per gram sediment, SE France. 48 records from Diatom assamblage in samples from sediment trap OG5. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD45. 3 records from Sarcodine counts and carbon biomass at station TT011_2-CTD21. 11054 records from Colección de Sifonápteros del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 1356 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 7 records from Boraginaceae (Cynoglossum cherangauiense). 13702 records from Fundación Miguel Lillo - Colección Ornitológica. 340 records from Occurrence of mammalia relicts at site Brillenhöhle. 15 records from Herdengelhoehle taxa and datings. 7 records from Radiolaria assemblage in sediment core GIK23424-3. 1 records from Microfossil abundance of Hole 42-378. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 4 records from Two new troglobiotic palpigrades (Palpigradi: Eukoeneniidae) from Brazil. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 1447 records from Odonata of the Congo River 2010 expedition. 7950 records from European riparian ground beetles. 2877 records from Flea collection of Slovenian Museum of Natural History (Slovenia only). 2247 records from NIAES microbial inventory, "microForce" microbe collection, Tsukuba, National Institute for Agro-Environmental Sciences, Japan. 5575 records from Estudios bióticos: plantas, edafofauna epígea, anfibios y aves en los complejos de páramos los Nevados y Chilí-Barragán. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_1-CTD8. 45 records from Wasser-Lernort Nettemündung. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 8200 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 156 records from (4) Assemblages of planktic foraminifera and Sea Surface Temperature (SST) reconstructed from the Modern Analogue Technique in sediment core MD02-2488 during the Last Interglacial. 60 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Steffen Matezki. 7684 records from Seed bank grassland. 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 3343 records from SMNS Palaeontological collection - Fossil aquatic vertebrates. 7 records from Range table from planktonic foraminifers in ODP Hole 192-1185B. 1312 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 157 records from Contribution to the knowledge of Chinese Phasmatodea III: Catalogue of the phasmids of Hainan Island, China, with descriptions of one new genus, one new species and two new subspecies and proposals of three new combinations. 157 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 14590 records from Biodiversidad mastozoológica del Eje Volcánico Transversal. 3 records from A new species of the genus Leptobrachium (Anura: Megophryidae) from the Gaoligongshan Mountain Range, China. 21572 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Guantiva - La Rusia. 57 records from Heidesee / Halle. 50 records from Plasm bearing foraminifera counts of multinet SO118_MSN1267. 112 records from Total foraminifera counts of multinet M11/1_MSN526. 1250 records from Colección de Crustáceos Macrobénticos del Golfo de México (ICMyL-DF, UNAM). 1537 records from (Table 3) Distribution of planktonic foraminifers in ODP Hole 108-657A. 268 records from (Table 5) Relative abundance of benthic foraminifera in ODP Hole 112-686A. 471 records from (Table 3) Distribution of planktonic foraminifera in ODP Hole 183-1138A, Part III. 777 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 23146 records from BC Coastal Waterbird Survey. 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 70704 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1988) (AfrOBIS). 46933 records from Botanical Museum, Copenhagen, Mycology Herbarium. 808 records from (Table 2) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 113-690C on Maud Rise, Weddell Sea. 42 records from Foraminifera abundance of Hole 24-236. 1843 records from (Table 3) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 3535 records from Colección de Entomología Médica del Instituto Colombiano de Medicina Tropical. 490 records from flower availability 2007 Schwäbische Alb. 5338 records from CHAS Mammalogy Collection (Arctos). 2097 records from Base de datos de la familia Cactaceae de la Península de Baja California, México. 1 records from Nothrus scaliger. 46 records from Foraminifera species abundances from tow TT007_5-MOC9. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_11-CTD137. 212 records from Nanoplankton abundance at station GeoB2017-1. 180 records from Range table from ostracoda in ODP Hole 144-871A. 9 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/091-4. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/546-2. 116 records from (Table 17) Distribution of planktonic foraminifers in ODP Hole 108-668B. 256 records from (Table 4) Distribution of Cretaceous calcareous nannofossils in ODP Hole 114-700B. 1680 records from Estudio comparativo del zooplancton en dos regiones de México. 355 records from (Table A3) Semi-quantitative frequency of Globorotalia menardii in core SO164-17-2. 2241402 records from Biologiezentrum Linz. 655 records from Planktic foraminifera assemblage in sediment core GIK17049-6. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 944 records from Range table from planktonic foraminifers in ODP Hole 192-1183A. 72 records from Range table from benthic foraminifers in ODP Hole 198-1213A. 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 2212 records from Collection Polychaeta - ZSRO. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 100 records from Birdrace-The_Ringers-Friesland. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 176 records from Total foraminifera counts of multinet M21/2_MSN656. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 11 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_236-1. 31 records from Biological data measured on water bottle sampels at station AT_II-119/5_31-7. 40 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2215-1. 134 records from Coleoptera identified from the Bellot Street site, Greenwich, London. 1634 records from ZFMK DORSA. 349 records from Planktic foraminifera counts of sediment core V20-170. 6659 records from Anfibios y Reptiles del Estado de Tamaulipas, México (UANL). 149 records from A multi-proxy investigation of sediment core GeoB7165-1 ~60 km offshore Concepción. 8684 records from Individual Sightings. 94474 records from TNHC Herpetology Collection. 66 records from Visual Plants (144.41.33.158) - Private collection of Thorsten Kroemer. 15074 records from NBMP Field Survey. 105 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 172 records from Foraminifera abundance of Hole 59-448A. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 50703 records from Seasearch Marine Surveys in Ireland. 3224 records from Relative abundance of planktic foraminifera in sediment core GeoB1312-2. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 77 records from ZUEC-AST - Coleção de Asteroidea do Museu de Zoologia da UNICAMP. 3057 records from Florida Keys Reef Visual Census 2010. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 163 records from Total foraminifera counts from multinet SO119_MSN1285. 11 records from Content of coarse fraction and G. menardii in sediment corev V25-39. 591 records from Planktic foraminifera counts of sediment core V16-25. 2073 records from Bryophyte collection of Jyväskylä University Museum. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 1134 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 115 records from (Table 2a) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Canary upwelling. 168 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2009. 1150 records from Macrozooplankton concentrations estimated from MOCNESS tow samples, Continental Margin Western Antarctic Peninsula, GLOBEC. 1101 records from Relative abundance of ostracods in sediment core Co1202. 19 records from Microplankton data off Mejillones, 2006, Chile. 98 records from Distribution of palynomorphs in Miocene sediments of ODP Site 188-1165 in the Prydz Bay, East Antarctica (Table 1). 218518 records from Mammalogy Collection - Royal Ontario Museum. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 139 records from Siliceous microfossil occurrence, Site 177-1093. 14533 records from MVZ Egg and Nest Collection (Arctos). 486 records from UAM Herpetology Collection (Arctos). 5262 records from Spider Mites Collection of Jean Gutierrez. 1968 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 228 records from Herbier Flora selecta exsiccata publié par Ch. MAGNIER (BOUM). 15 records from Fiocruz/CENT - Coleção de Enterobactérias. 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 1 records from Nothrus pollinosus. 255 records from GENT Lactarius Deliciosi. 1733 records from Birds collection of Abiko City Museum of Birds. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 91 records from BIRDRACE SchrägeVögel. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 112 records from Benthic foraminiferal assemblage (dead) in MUC SC2-L, size fraction 63-150 µm. 169 records from Planktic foraminifera counts at CTD station PS55/051. 32 records from Microzooplankton abundance measured on water bottle samples at station PS65/593-3. 1055 records from Macro benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 1409 records from Planktic foraminifera counts of sediment core AB000280. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 495 records from Field Study Group of the Dutch Mammal Society (NL) - 2013 - Mammal Survey Western Rhodopes, Bulgaria. 25 records from A new Gymnotus (Teleostei: Gymnotiformes: Gymnotidae) from the Pantanal Matogrossense of Brazil and adjacent drainages: continued documentation of a cryptic fauna.. 21 records from Unveiling of a cryptic Dicranomyia (Idiopyga) from northern Finland using integrative approach (Diptera, Limoniidae). 3 records from A new spider species, Heser stoevi sp. nov., from Turkmenistan (Araneae: Gnaphosidae). 344 records from (Table T13) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones Palpha-P3b. 31030 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 1835 records from ARKO Overvåking kalklindeskog. 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 568 records from Expedición Providencia I - INVEMAR. 76 records from Faunal assemblage of sediment core GS7603-10. 64 records from Total foraminifera counts of multinet M42/3_MSN1369. 8 records from Phytoplankton abundance at station Rigel_6_2005-03 in March 2005, Chipana, Chile. 9 records from Nannofossil abundance of Hole 1-2. 36 records from Nannofossil abundance of Hole 14-141. 596 records from Planktic foraminifera counts of sediment core A15-558. 2792 records from Birds (UWEP-BI). 1298 records from Planktic foraminifera abundance of Hole 23-219. 2029 records from National Trust - Sutton Hoo species data held by The National Trust.. 38 records from (Table 1c) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the finishing of the Late Neopleistocene activity phase of the Keli Volcanic Highland. 222 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment II deployed at station PS64/475-1 during ARK-XIX/3c. 26403 records from EWT: African Crane Conservation Programme Sightings. 1 records from Nouvelles fourmis d'Afrique.. 1 records from A new generic name, Semigothograptus, for Gothograptus? meganassa Rickards & Palmer, 2002, from the Silurian post- lundgreni Biozone recovery phase, and comparative morphology of retiolitids from the lowermost upper Homerian (upper Wenlock). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Formicariidae. 1506 records from Computarización de la Colección de Referencia para Zoología, Arqueozoología y Paleontología del Museo de Historia Natural de la Universidad Autónoma de Baja California Sur. 1581 records from Collection of Occurrence data on mammal species during wildlife census in W Biosphere Reserve in 2013 and 2015. Data mobilized in the framework of the BID-AF2015-0030-SMA project of Isidore Amahowe. 73 records from AMF colonization in Plantago. 6 records from Coleção de Tardigrada do Museu Nacional - UFRJ. 6086 records from Computarización de las colectas del estado de Morelos depositadas en el Herbario HUMO de la Universidad Autónoma del Estado de Morelos. 8565 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 10 records from A new species and new records of Molophilus Curtis, 1833 (Diptera: Limoniidae) from the Western Palaearctic Region. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 6717 records from LSUMZ Mammal Tissues. 171 records from Total foraminifera counts of multinet M42/3_MSN1370. 85 records from Birdrace-Die_Paradiesvögel-Herford. 3 records from Taxonomy of European Damaeidae (Acari: Oribatida) II. Porobelba weigmanni n. sp. (Oribatida, Damaeidae), from East Slovakia, with comments on other known species of the genus. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 135 records from (Table A.08) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (80-150 µm). 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/580-2. 2184 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 84 records from Benthic foraminifera abundance of Hole 84-566C. 38 records from Microfossil abundance of Hole 21-206C. 1794 records from Herbarium BSG Lichenes. 9138 records from CRI - Herbário Pe. Dr. Raulino Reitz. 24121 records from Endemic plants of the Congo basin. 17 records from Hazel Dormouse in Ireland. 504 records from Schatzinsel Wangerooge. 129 records from Nannofossil abundance of Hole 29-284. 28 records from (Table 4) Range chart of calcareous nannofossils from Ross Sea sediment cores. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 8523 records from Distribution of planktic foraminifers of core RC24-16. 379 records from Relative abundance of planktonic foraminifera in sediment core MK-325. 336 records from Scottish Natural Heritage - Site Condition Monitoring Records from surveys of lamprey species in five river SACs in Scotland. 5944 records from (Figure 6) Distribution of benthic foraminifers in middle-upper and Quaternary in DSDP Site 71-512. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 1088 records from (Appendix 2-1) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 7-62A in the western Pacific Ocean. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 35 records from Nannofossil abundance of Hole 78-543. 6 records from Nannofossil abundance of Hole 6-49. 7 records from Nannofossil abundance of Hole 38-336. 2000 records from Shellfish (ASJK_MS). 145 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE275. 2577 records from Avifauna de la Isla de Cozumel, Quintana Roo_3. 15006 records from Flora del Valle de Tehuacán-Cuicatlán: II Fase. 1166 records from South Western Pacific Regional OBIS Data Bio Ross Subset (South Western Pac ific OBIS). 82756 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1992) (AfrOBIS). 274 records from Herpetological Collection at the Wildlife Institute of India Vertebrate Museum. 3161 records from Distribution of foraminifera of sediment core ENAM93-21. 7457 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 116 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (75° N section). 15 records from Pogonophora collection of National Museum of Nature and Science. 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 782116 records from Royal Botanic Garden Edinburgh Herbarium (E). 1 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Sturnidae. 44 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America Part I. Genus Scatopsciara Edwards, 1927. 54 records from Herbier de l'Ecole Normale de Bourges (BOUM). 97 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 363 records from Registros de plantas obtenidos en el monitoreo de una de las plataformas instaladas por CORNARE en Antioquia. 3512 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 15506 records from Actualización del banco de datos florístico de la Península de Yucatán (BAFLOPY). 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 173 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 216 records from Range table from benthic foraminifers in ODP Hole 198-1207A. 1 records from Dinoflagellate abundance of Hole 19-183. 8276 records from Herbario de la Universidad Pública de Navarra, Pamplona: UPNA-H. 681 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 2 records from High diversity of Caligus species (Copepoda: Siphonostomatoida: Caligidae) in Taiwanese waters. 700754 records from Waarnemingen.be - Plant occurrences in Flanders and the Brussels Capital Region, Belgium. 40 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 55317 records from Local Wildlife Site Surveys Berkshire. 27 records from synthese_Protistdiversity_KG. 318 records from Geometry of coccolith Coccolithus pelagicus in ODP Hole 104-643A. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 371 records from Planktic foraminifera abundance of Hole 63-470. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 ( Araneae , Tetragnathidae ) with notes on habits and conservation status. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 39 records from Red list project inventory, fungi. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 300 records from Estudio monográfico de los gasteromicetos del noroeste de Baja California, México. Provincia Californiana. 3468 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-158-1. 16 records from Nannofossil abundance of Hole 9-77B. 8 records from Nannofossil abundance of Hole 49-409. 2 records from Range table from nannofossils in ODP Hole 198-1207A. 22 records from Steinbruch Mainz-Weisenau, 4.Jahr. 26 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 1458 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 1380 records from Range table from benthic foraminifers in ODP Hole 189-1168A. 90 records from Collection Ctenophora SMF. 351058 records from Staffordshire Ecological Record - SER Species-based Surveys. 1584 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 32 records from Ice Zooplankton Beaufort Sea. 71 records from Distribution of benthic abyssal gastropods in the Iberian Deep-Sea Basin (Table 2). 14 records from (Table 1) Analyses of coarse fraction of DSDP Hole 94-609. 5612 records from Marine Biological Association - 2005-Ongoing United Kingdom MarLIN Shore Thing timed search results. 36 records from Range table from planktonic foraminifers in ODP Hole 144-877A. 13593 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 236831 records from KU Museum of Invertebrate Paleontology. 359044 records from Insect (KNAM-IN). 43 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM5. 18 records from Nandus prolixus, a new species of leaf fish from northeastern Borneo (Teleostei: Perciformes: Nandidae).. 1 records from Zetes morticinus. 59967 records from Tasmanian Museum and Art Gallery provider for OZCAM. 6 records from Mammalia (JNHM-MM). 95 records from Vielfalt verschiedener Wiesen. 3 records from Blankenfelder See. 65 records from BIRDRACE Federal Birds of Investigation FBI. 248 records from Schulgarten der Volksschule. 33 records from Schüler erforschen die Helme-Aue. 50 records from Total foraminifera counts of multinet M21/5_MSN743. 45 records from (Table A.09) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (125-250 µm). 260 records from Range table from ostracoda in ODP Hole 144-873B. 7 records from Appendicularia abundance of station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 2). 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 4774 records from Estudio de la avifauna y de las interacciones ave-planta en la Reserva de la Biosfera de la Barranca de Metztitlán Hidalgo, México. 2184 records from Caracterización y estructura de la ictiofauna de arrecifes rocosos y coralinos en Punta Carrizal, Colima, México para fines de inventario y conservación de la diversidad animal. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 61 records from Range table from benthic foraminifers in ODP Hole 139-857B. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 63646 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 56 records from Estetal (Buxtehude). 10 records from New species of Zenoria Mulsant (Coleoptera: Coccinellidae) from Brazil and Peru. 41308 records from TPWD HARC Texas Coastal Fisheries San Antonio Bay Trawl. 10075 records from Nematoda of Costa Rica (INBio). 18 records from Nivalios gen. nov. (Hemiptera: Fulgoromorpha: Flatidae), first record of the tribe Nephesini from China. 21 records from On the Lathrobium fauna of the Luoxiao Mountains, Central China. 2 records from A redescription of Lophostica mauriciana Simon, 1902 (Araneae: Salticidae). 98686 records from CAS Ornithology (ORN). 10 records from Maculabatis ambigua sp. nov., a new whipray (Myliobatiformes: Dasyatidae) from the Western Indian Ocean. 29 records from Abundance of Globorotalia menardii of sediment core GeoB2821-1. 147 records from Total foraminifera counts of multinet M10/2_MSN295. 100 records from Total foraminifera counts of multinet M12/3_MSN536. 1301 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-159-1. 12 records from Nannofossil abundance of Hole 20-200. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-093. 3 records from A new genus and species of Laelapidae (Acari: Mesostigmata) from Iran. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 580 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE272. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 1301 records from Collection Hymenoptera SMF. 15000 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 2 y 3. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_2-CTD16. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN743. 1 records from Microplankton counts and carbon biomass at station TT011_8-CTD96. 15 records from Occurrence of mammalia relicts at site Dendermonde. 50 records from Planktic foraminifera abundance of Hole 60-457. 730 records from MATRIX project, Budongo fragments birds. 920 records from Annotated list of observed birds in W and Pendjari Reserves in Benin, February 2010. Data mobilized in the framework of the BID-AF2015-0044-SMA project of GANGNIBO Charles. Project funded by EU. 242 records from Biología del murciélago mastín enano (Eumops bonariensis nanus) en Yucatán. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 11 records from Phytoplankton abundance at station Rigel_4_2005-03 in March 2005, Chipana, Chile. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 2634 records from Mega benthos in surface sediments sampled during POLARSTERN cruise ANT-XXIII/8. 2610 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Támesis, Antioquia. 502 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 41548 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1985) (AfrOBIS). 6987 records from Lyman Entomological Museum. 15886 records from Insect Specimen Database of Fukui City Museum of Natural History. 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 325 records from Planktic foraminifera abundance of Hole 32-305. 164 records from Planktic foraminifera abundance of Hole 94-610B. 3726 records from (Table 3) Relative abundance of benthic foraminifera in sediment profile HUD84-030-04. 221 records from (Table 1) Abundance of planktonic foraminifera in ODP Hole 113-689B, large size fraction. 85439 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1987) (AfrOBIS). 30000 records from Freshwater Fish Specimens of Lake Biwa Museum. 21348 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 1312 records from GEO-Hauptveranstaltung (Insel Vilm). 1 records from Nothrus theleproctus. 2 records from Range table from planktonic foraminifers in ODP Hole 144-874A. 17 records from A review of the genus Pareuchiloglanis (Sisoridae) from the Lancangjiang (upper Mekong River) with descriptions of two new species from Yunnan, China.. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 6 records from (Table 2) Miocene biostratigraphy of the Vierlandian stage in Schleswig-Holstein. 221 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Turdidae. 350 records from Speothos Venaticus por Guillermo Gil. 36188 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 491 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 116007 records from BMSM Bailey-Matthews National Shell Museum. 79717 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 106 records from Total foraminifera counts of multinet M42/3_MSN1365. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 5 records from Schulwald Regionale Schule Sprendlingen. 7 records from Nannofossil abundance of Hole 5-33. 14 records from Nannofossil abundance of Hole 8-72A. 2730 records from (Table 10) Distribution of planktonic foraminifera in the middle to late Miocene section of ODP Hole 149-900A. 68081 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1995) (AfrOBIS). 495 records from Life Science National Tsing Hua University. 7 records from Analyses of the recent components of sediment core PS1219-1. 239 records from Naturerlebnisraum Koppelsberg. 35 records from Occurrence of mammalia relicts at site Gura Cheii-Rasnov. 4 records from A new species of Auriculostoma (Trematoda: Allocreadiidae) from the intestine of Brycon guatemalensis (Characiformes: Bryconidae) from the Usumacinta River Basin, Mexico, based on morphology and 28 S rDNA sequences, with a key to species of the genus. 186 records from Planktic foraminifera abundance of Hole 94-610. 437 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 1093 records from Systematic studies on Pseudomyrmex acacia-ants (Hymenoptera: Formicidae: Pseudomyrmecinae). 4085 records from SMNS Palaeontological collection - Tertiary mammals. 1421 records from Weevils of Poland. 1 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 154 records from Censo aéreo de poblaciones de borrego cimarrón (Ovis canadensis cremnobates) en Baja California, México. 8594 records from ColRest_Raw1. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 233 records from Föhrenried (Fronreute und Baindt). 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 58 records from Total foraminifera counts of multinet M27/2_MSN882. 8063 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 7848 records from Lichen specimen database of Faurie collection. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 544 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD35. 5644 records from (Appendix 1) Planktonic foraminifera abundances in ODP Site 181-1123. 77 records from Occurrence of recent nannoplankton in sediment core M1_MULT242, Arabian Sea (Fig. 2). 7 records from Nannofossil abundance of Hole 9-82A. 3 records from Nannofossil abundance of Hole 22-212. 15 records from Microfossil abundance of Hole 59-450. 2478 records from (Figure 3) Range charts of selected dinoflagellate cysts in ODP Hole 122-762C. 94 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellates, pollen and spore abundance of Hole 29-283. 92 records from The Ants of Bulgaria. 4761 records from SMDB - Santa Maria Departamento de Biologia. 292 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 796 records from (Data S1) Palynology of IODP Hole 318-U1356A. 27847 records from Dataset of Passerine bird communities in a mediterranean high mountain (Sierra Nevada, Spain). 5164 records from Inventaire National du Patrimoine Naturel : Programme CARTHAM: Inventaire biologique dans le cadre de Natura 2000 en Mer. 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 152 records from Nematode abundances in sediments from the Nyegga pockmark area (Norwegian Sea) obtained during the VICKING expedition in 2006. 16 records from New records of doryctine wasps (Hymenoptera: Braconidae) from Argentina, with the description of Shawius diiorioi Martínez sp. nov.. 2093233 records from Museum of Comparative Zoology, Harvard University. 22 records from Review of amphipods of the Melita group (Amphipoda: Melitidae) from the coastal waters of Sakhalin Island (Far East of Russia). III. Genera Abludomelita Karaman, 1981 and Melita Leach, 1814. 820 records from Brood cell No. of trap-nesting species Alb 2008. 152 records from Abundance of planktic foraminifera at CTD station M39/4_402CTD-55. 783 records from Phytoplankton abundance in surface water during cruise CD61. 62 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 70 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/357-1. 279 records from BIRDRACE Wannacks Topti(c)ker. 9 records from Coccolith counts of multinet M32/5_MSN982. 8372 records from UWBM Herpetology Collection (Arctos). 415 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE206. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 85 records from Fig 14. Pollen profile from sediment core Schmiecher See. 77 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2009. 164357 records from The Himalayan Uplands Plant database (HUP Version 1). 17374 records from Canadian Museum of Nature Amphibian and Reptile Collection - Anura. 19164 records from The Gordon Alexander Orthoptera Collection. 3 records from Acari fossil - SMNG. 41 records from Altholzparzelle Eilenriede Hannover. 125 records from Artenbestimmung. 135 records from Range table from planktonic foraminifers in ODP Hole 180-1114A. 172 records from Redescription of Gymnotus coropinae (Gymnotiformes, Gymnotidae), an often misidentified species of Neotropical electric fish, with notes on natural history and electric signals.. 116 records from Deep-sea (> 1000 m) Goniasteridae (Valvatida; Asteroidea) from the North Pacific, including an overview of Sibogaster, Bathyceramaster n. gen. and three new species. 1 records from Pelops fuligineus. 152 records from On the genus Trachysalambria Burkenroad, 1934 (Crustacea, Decapoda, Penaeidae), with descriptions of three new species. 16246 records from Herbarium Erlangense. 1888 records from Inventario de los crustáceos decápodos asociados al ecosistema coralino de Pocillopora en el Pacífico tropical mexicano. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 10415 records from Collection Cnidaria SMF. 5 records from Nannofossil abundance of Hole 84-569. 54 records from (Table 3) Distribution of nannofossils in DSDP Hole 87-583A. 1129 records from Mollusca Collection of Saitama Museum of Natural History. 775 records from Insect (GNHM-IN). 240 records from (Table 2) Distribution of Lower Cretaceous calcareous nannofossils in ODP Hole 123-766A. 15 records from (Table T1) Lithology and palynomorphs of neogene sediments of ODP Hole 178-1095B. 1575 records from Inventario de la vegetación acuática vascular de la reserva de la biosfera Pantanos de Centla, Tabasco. 1293 records from Base de datos y catálogo de helmintos parásitos de anuros de México. 354 records from Foraminifera distribution of sediment core KS310. 24 records from Range table from planktonic foraminifers in ODP Hole 143-865A. 462 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 21 records from Hypostomus rhantos (Siluriformes: Loricariidae), a new species from southern Venezuela.. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 187800 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 16 records from Abundance of epibenthic echinoderms at seafloor photography station PO196_1024. 486 records from Corales de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMco). 18 records from Redescription of two species of wobbegongs (Chondrichthyes: Orectolobidae) with elevation of Orectolobus halei Whitley 1940 to species level.. 4 records from Nannofossil abundance of Hole 52-418. 82 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-699. 126 records from (Appendix F) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-749C. 593 records from Ostracoda in sediment core PS51/159-10. 1000 records from Estudio taxonómico-florístico de la familia Orchidaceae en el Bajío: tribus Epidendrae y Maxillariae. 900 records from Manual ilustrado de las orquídeas silvestres del estado de Morelos. 1272 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 21129 records from Pteridophyta specimens of Shizuoka Prefecture Museum of Natural History. 3 records from Planktic foraminifera abundance of Hole 54-424B. 10 records from Range table from planktonic foraminifers in ODP Hole 169-1038A. 35517 records from NMSA: Arthropod Collections (1900-2012). 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 13 records from Review of the genus Chrysoscota in Cambodia (Lepidoptera, Erebidae, Arctiinae), with description of a new species. 66 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 55 records from Galls on Beech Trees in Hainich, 2008. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 308 records from Wangerooge. 233 records from Total foraminifera counts from M35/1_MSN1044. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_2-CTD26. 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 907 records from Actualización sistemática y electrónica del acervo de gasterópodos de la Colección Malacológica Dr. Antonio García-Cubas (COMA), del Instituto de Ciencias del Mar y Limnología, UNAM. 2299 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 103 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 15 records from Kühnauer Aue und Kühnauer See. 21 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD13. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 149 records from Bayerische Donau - Neu Ulm. 143 records from Akita Prefectural Museum＋Malacostracans Specimens of Akita Prefectural Museum. 675 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 324 records from (Appendix B) Planktic foraminiferal assemblages from ODP Holes 113-689B and 113-690B. 18 records from Plasm bearing foraminifera counts from multinet M31/2_MSN897. 1 records from Papilio Sticheli nov. spec. aut subsp.. 299 records from Korean Insect Database (Hymenoptera: Ichneumonidae). 5 records from Analyses of the recent components of sediment core PS1216-1. 181 records from Nematode abundance of the Eastern Mediterranean Sea in cold seep sediments collected during MSM13/3 and MSM 13/4 cruises (2009). 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 56 records from Zitadelle Berlin-Spandau (7b). 159 records from Total foraminifera counts of multinet SO118_MSN1251. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 122 records from Relative abundance of benthic foraminifera of sediment core GIK13292-3, East Atlantic off Senegal and Gambia (Table 3). 42 records from BID-AF2015-0004-NAC - DENOMBREMENT SIMULTANE ET SYNCRONISE DES OISEAUX D’EAU MIGRATEURS AU TOGO. 360 records from Order Araneae. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 80 records from BB-Biodiversität b. 3 records from Nannofossil abundance of Hole 9-80. 12 records from Diatom abundance measured on water bottle samples at station PS58/011-3. 7311 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 3653 records from A Dataset of Deep-Sea Fishes Surveyed by Research Vessels in the Waters around Taiwan. 63 records from GenLink - Genetic diversity of Veronica chamaedrys. 2984 records from USGS Marine Fishes of St. Croix and U.S. Virgin Islands. 7 records from Range table from planktonic foraminifers in ODP Hole 182-1132A. 226 records from Range table from benthic foraminifers in ODP Hole 182-1130A. 240 records from Range table from nannofossils in ODP Hole 199-1219A. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 300 records from A systematic revision of the genus Archocentrus (Perciformes: Cichlidae), with the description of two new genera and six new species.. 2 records from First record of Viannaiidae (Nematoda: Trichostrongylina) in fossorial rodents (Ctenomys spp.) from Central Argentina, with description of a new genus and species. 209 records from ZUEC-APL - Coleção de Aplacophora do Museu de Zoologia da UNICAMP. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 4778 records from ZUEC-GAS - Coleção de Gastropoda do Museu de Zoologia da UNICAMP. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 28 records from Stadtpark Prinzengarten (Sigmaringen). 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 27 records from Sistemática molecular de Trogoniformes (Aves): Filogenia del orden y análisis de variabilidad genética de quetzales en la reserva de la Biosfera El Triunfo. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 165 records from Total foraminifera counts from multinet M31/3_MSN903. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 5 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-10-12. 5 records from A new species of Nanochromis (Teleostei: Cichlidae) from Lake Mai Ndombe, central Congo Basin, Democratic Republic of Congo.. 22 records from Phytoplankton abundance at station Rigel_6_2005-05 in May 2005, Chipana, Chile. 5841 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 5265 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 238 records from Coccoliths in ODP Hole 104-643A. 10 records from Two new butterfly species (Lepidoptera: Rhopalocera) from Mount Cameroon, Gulf of Guinea Highlands, Cameroon. 32 records from Nannofossil abundance of Hole 67-499. 316 records from Planktic foraminifera counts of sediment core RC11-86. 2210 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 410 records from (Appendix 3) Planktonic foraminiferal composition from ODP Site 172-1056. 122 records from Review of the ant genus Aenictus (Hymenoptera: Formicidae) in Australia with notes on A. ceylonicus (Mayr).. 16 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 4 records from Carcinoplax fasciata, a new species of deep-water goneplacid crab from southwestern India (Crustacea: Decapoda: Brachyura: Goneplacoidea). 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 2 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 703 records from Planktic foraminifera counts of sediment core V25-59. 4148 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 388 records from SNH Invertebrate Site Condition Monitoring 2013/14: Ben Lomond SSSI. 6 records from Free-living marine nematodes of Desmodorella and Zalonema (Nematoda: Desmodoridae) with description of two new species from the deep sea of the North Western Pacific. 97 records from Occurrence of mammalia relicts at site Rejtek 1. 2238 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 24 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171C. 2 records from DNA barcoding reveals a new record of Potamogeton distinctus (Potamogetonaceae) and its natural hybrids, P. distinctus × P. nodosus and P. distinctus × P. wrightii (P. ×malainoides) from Myanmar. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 133 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Parulidae. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 86 records from Plasm bearing foraminifera counts from M35/1_MSN1061. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 316 records from Hymenoptera, NEF. 140 records from (Table 2b) Downcore distribution of live benthic foraminifera of sediment core PS1394-3, Weddell Sea. 21 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, >150 µm. 133 records from Total foraminifera counts of multinet M21/3_MSN676. 2 records from Benthic hard-bottom communities abundance at Lilliguapy in 2010. 15 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 2 records from Nannofossil abundance of Hole 29-280A. 46 records from Antarctic Isopods. 2827 records from (Figure 5) Distribution of benthic foraminifers in the upper Eocene, Oligocene, and Quaternary of DSDP Hole 71-511. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 222 records from SNH Invertebrate Site Condition Monitoring 2013/14: Crathie Wood SSSI. 26 records from SNH Invertebrate Site Condition Monitoring 2013/14: Loch Lubnaig Marshes SSSI. 637 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales de Bahía Málaga, municipio de Buenaventura, Valle del Cauca. 1076 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Tuluá, Valle del Cauca. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 1 records from Zetes gilvulus. 317 records from Planktic foraminifera counts of sediment core RC14-29. 35 records from Ortsrand Zandershagen. 149 records from (Table 2a and b) Median abundances of macrobenthos in surface sediments. 8775 records from (Table 2) Occurrences of planktonic foraminifers in samples from ODP Hole 105-647A. 4 records from Akita Prefectural Museum＋Annelids Specimens of Akita Prefectural Museum. 1597 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Historico_cofc). Facultad de Ciencias. Universidad de Córdoba. 4244 records from Insect Specimens of Lake Biwa Museum. 18192 records from Plant Specimens of The Shimane Nature Museum of Mt. Sanbe. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 21261 records from Sukkulentensammlung Zürich. 1 records from H. Sauter's Formosa-Ausbeute: Formicidae (Hym.).. 1 records from Nothrus posticus. 5 records from Revision of the coral-inhabiting genus Conopea (Cirripedia: Archaeobalanidae) with description of two new species of the genera Conopea and Acasta. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 89 records from Birdrace-Team_Wangerooge-Friesland. 781 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 85 records from Sedimentological investigation on core V25-45. 3 records from Sarcodine counts and carbon biomass at station TT011_15-CTD168. 6 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 122 records from Phytoplankton abundance at station CD46_1005C#4. 1 records from Mamíferos marinos de la Reserva de Biósfera Seaflower. 482 records from Kühmark bei Wetzlar. 31 records from Nannofossil abundance of Hole 4-23. 81 records from Foraminifera species abundances from tow TT011_6-MOC65. 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 34253 records from MedOBIS (EurOBIS). 1 records from Berlese's Primitive Oribatid Mites. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1400-4. 353 records from Stadtgebiet (Dannenberg). 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR72. 29 records from Occurrence of mammalia relicts at site la Grotte du Thai. 36 records from Occurrence of mammalia relicts at site Trebacki krs. 16 records from Abundance of radiolaria at station LV28-3-3. 60 records from Planktic foraminifera abundance of Hole 19-192. 53 records from Programa regional para la caracterización y el monitoreo de ecosistemas de manglar del Golfo de México y Caribe Mexicano: Península de Yucatán. 1 records from Nothrus pulverulentus. 544 records from Naturalis Biodiversity Center (NL) - Foraminifera. 6 records from Across the Baltic: a new record for an enigmatic black scavenger fly, Zuskamira inexpectata (Pont, 1987) (Sepsidae) in Finland. 588 records from Fiocruz/COLTRYP - Coleção de Trypanosoma de Mamíferos Silvestres, Domésticos e Vetores. 100 records from Grenzturm Hohen Neuendorf. 180 records from Paul-Gerhardt-Schule Dassel. 40 records from Tiere und Pflanzen um uns herum !. 135 records from Waldi-Weiher. 5 records from Fledermäuse u. nachtaktive Insekten. 269 records from BIRDRACE Dithmarscher Deichhühner. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 69 records from Mönchspark. 119 records from Kinorhyncha. 10 records from Microzooplankton abundance and biomass at station TT043_21-22. 6 records from Microzooplankton abundance and biomass at station NBP97-08-28-1. 7 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 2 records from Nannofossil abundance of Hole 7-64A. 3224 records from (Appendix C) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-748B. 581051 records from Swiss National Butterflies Databank. 1236 records from Percentages of planktonic foraminifera species in sediment core V30-40. 2 records from List of the specimens of dipterous insects in the collection of the British Museum. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1208 records from Relative abundances of middle Pleistocene benthic foraminifera in ODP Site 181-1125. 83 records from Abundance of birds on the channels of Lena Delta in the brood period. 12 records from A new species and new records of Hentzia (Araneae: Salticidae: Dendryphantinae) from the United States. 2654 records from Collection of Hymenoptera. 1683 records from (Appendix 2) Distribution of planktonic foraminifera in the last 70 kyr of sediment core MD95-2043 from the western Mediterranean Sea. 7 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 429 records from Larval fish at Helgoland Roads in 2004. 1404 records from (Table 1) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-762C, Part III. 468 records from Range table from planktonic foraminifers in ODP Hole 155-932A. 7054 records from Inventario florístico y base de datos de la Reserva Ecológica Sierra de San Juan, Nayarit, México. 185 records from Abundance of coccosphere-units of site GIK23414. 9 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 23 records from Landwehrbach. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 112 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2009. 1 records from A historical review of the classification of Erebinae (Lepidoptera: Erebidae). 5 records from A new monotypic genus, a species synonymy and nomenclatural corrections in the arid-adapted Canthonini (Scarabaeidae, Scarabaeinae) from the Succulent Karoo Biome of south-western Africa. 48 records from Benthic foraminifera abundance of Hole 42-380A. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_8-CTD102. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 483 records from Artenvielfalt im Rhein-Neckar-Raum. 4 records from Nannofossil abundance of Hole 16-156. 92 records from Nannofossil abundance of Hole 31-296. 7 records from Nannofossil abundance of Hole 27-259. 90 records from Planktic foraminifera counts of sediment core RC13-158. 704 records from Planktic foraminifera counts of sediment core V18-207. 8336 records from Birds (GMBO-BI). 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 465 records from Philosophenwald und Wieseckaue in Gießen. 47 records from Lepidurus arcticus survey Northeast Greenland 2013. 83 records from ZUEC-POR - Coleção de Porifera do Museu de Zoologia da UNICAMP. 1097 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 692 records from Collection Trilobita SMF. 92 records from Nottekanal, Klasse 7 - 10. 203 records from Planktic foraminifera abundance of Hole 72-515B. 525 records from Benthic foraminifera abundance of Hole 40-360. 892 records from Weevils of Wales and England. 358 records from Apectodinium, age and percentage of endemic and bipolar dinoflagellate cysts of IODP Hole 318-U1356A. 234 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 2. 223320 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 14 records from First description of the male of the spider Tibellus paraguensis Simon, 1897 (Araneae: Philodromidae), with new distribution records. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 57 records from Eight new species of MacvIcarIa Gibson and Bray, 1982 (Digenea: Opecoelidae) mainly from endemic temperate marine fishes of Australia. 127226 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 8629 records from National Taiwan University. 181 records from Alien Species in Poland - Animals. 76 records from BIRDRACE Nachtigallen. 12 records from Art´n Vielfalt im Kinderwald. 773 records from Distribution of calcareous foraminifers in sediment core Well 6406/11-1. 198 records from Total foraminifera counts from M35/1_MSN1047. 1 records from Celaeno detrita. 49 records from (Appendix 1) DSDP Site 94-607A ostracode species census data. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-020. 11 records from Benthic macrofauna abundance of sediment core 13077-087. 175 records from Neißetal. 1148 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 1386 records from Red list project inventory, lichens. 2863 records from Invertebrates compiled by W.Block. 58 records from Lüner Holz (Lüneburg). 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 1335 records from MCNH Museum of Cultural and Natural History Mammals Collection. 2274 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 7 records from Megafauna biomass in surface sediment during cruise PLG95A. 6 records from Una nuova specie di Eupolybothrus della fauna di Grecia (Chilopoda, Lithobiomorpha). 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 243 records from Las tortugas marinas y sus playas de anidación en México. 9 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 80 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais do Centro Universitário Univates (ZOUMCN-UNIVATES). 23193 records from HRCB - Herbário Rioclarense. 20043 records from Mollusca collection of National Museum of Nature and Science. 197791 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 12 records from New Leucettidae de Laubenfels, 1936 (Porifera, Calcarea) from Western Australia. 22041 records from CUMV Mammal Collection (Arctos). 79 records from Umgebung von Schorndorf. 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 49 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Amphipods. 707 records from Benthic foraminiferal assemblages of Upper Cretaceous sediments from DSDP Hole 74-527 in the Angola Basin, South Atlantic Ocean (Table I, Appendix II). 1402 records from Free-living marine Nematodes from Puerto Madryn and Pozo sandy beaches (Chubut, Argentina), 2006.. 3 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 6887 records from (Figure 13) Distribution of middle Miocene through middle Pleistocene planktonic foraminifera in ODP Hole 132-810C. 328 records from Diseño, planeación y manejo sustentable de ecoturismo. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 61 records from BIRDRACE Baumläufer. 7346 records from MfN - Fossil vertebrates III. 20 records from Nannofossil abundance of Hole 7-63A. 5 records from A Redescription of Conoppia palmicinctum (Michael, 1880) (Acari, Cryptostigmata). 15675 records from Institut Botanic de Barcelona, BC-Histórico. 191 records from Foraminifera abundance of sediment core C1960.202. 12006 records from UCM Bird Collection (Arctos). 1 records from Oribates ovalis. 41 records from Nine genera of Eucnemidae (Coleoptera) new to Peru, with a key to Peruvian genera. 1807 records from Collection Paläobotanik SMB. 1371 records from Planktic foraminifera assemblage in sediment core GIK16773-1. 10 records from A new burrowing crayfish of the genus Fallicambarus Hobbs, 1969 (Decapoda: Cambaridae) from the Red River Drainage of the southcentral United States. 678 records from NCC Berkshire Chalk Grassland Survey 1985. 1 records from Nothrus bicarinatus. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 1016 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 7551636 records from BirdLife Australia, Birdata. 60 records from Schafsweide Seniorenhaus Berghof. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 84 records from Anisopodidae and Thaumaleidae (Diptera: Nematocera) of Ireland. 6 records from Microplankton counts and carbon biomass at station TT012_5-CTD35. 15 records from Abundance and composition of meiobenthos in surface sediments at Fladen Ground stations in August 1975, North Sea (Table 4). 10 records from Zoobenthos in surface sediments during Professor Vodyanitskiy cruise PV32. 31 records from Bayerische Donau - Tapfheim. 1026 records from Determinación del estado de las poblaciones silvestres del cocodrilo de pantano (Crocodylus moreletii) en México y evaluación de su estatus en la CITES. 21 records from (Figure 6) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-540. 72 records from (Table 5) Distribution of nannofossils in DSDP Hole 87-583F. 14 records from Nannofossil abundance of Hole 14-140. 4 records from Range table from nannofossils in ODP Hole 139-857A. 7 records from Phytoplankton abundance measured on water bottle samples at station PS65/466-2. 10 records from Benthic macrofauna abundance of sediment core 12930-059. 63 records from Planktic foraminifera counts of sediment core V19-21. 33403 records from Colección de Entomología del Museo de Ciencias Naturales de Tenerife: TFMC-EN. 1148 records from Southern Ocean Ostracoda (except Halocypridina). 42 records from Chaetognatha - SMF. 906 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 941 records from Pteridophyta specimens of Iwate Prefectural Museum. 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 5634 records from CeDoc de Biodiversitat Vegetal: BCN-Phycophyta. 35548 records from Herpetology. 122 records from Kelp rafts in the Southern Ocean (Australian Antarctic Data Centre). 49 records from Checklist of Fishes from Madagascar Reef, Campeche Bank, México. 20 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area II. 2630 records from Planktic foraminifera abundance of Hole 68-502A. 93 records from Range table from planktonic foraminifers in ODP Hole 180-1111A. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 313 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_93MC. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 6816 records from English Nature Oxfordshire Invertebrate Surveys. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Procellariidae. 1013 records from Planktic foraminifera counts of sediment core RE5-034. 180988 records from LSUMZ Birds Collection. 296 records from (Appendix 1c) Abundance and stable oxygen and carbon isotope ratios of Globigerinoides ruber from MIS 11 of sediment core GeoTu_SL096. 27 records from Pollen data of trap CB3. 19 records from (Table 1) Planktonic foraminifer abundance and stable isotope ratios of a sediment core near Baddeckenstedt, north Germany. 797 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV23. 94 records from (Table 1) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Sea of Okhotsk side). 112 records from Landschaftsschutzgebiet Hexenberg (Erftstadt-Erp). 106 records from Arteninventar rund um den Rannahof. 27 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 1 records from Occurrence of mammalia relicts at site Ejstrup. 786 records from Planktic foraminifera abundance of Hole 72-518. 385267 records from Natural History Museum, University of Tartu. 1963 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 124 records from Range table from benthic foraminifers in ODP Hole 189-1171A. 45 records from New taxa of Carpomyini, with special emphasis on Goniglossum (Diptera: Tephritidae: Trypetinae). 1661 records from Arácnidos de Centroamérica. 638 records from Geochemistry and sedimentology on core PO200/10_21-1. 1046 records from (Appendix Table 4) Number of planktonic foraminiferal specimens within species in Late Creatceous sediments of ODP Hole 122-763B from the Exmouth Plateau, eastern Indian Ocean. 35 records from Range table from planktonic foraminifers in ODP Hole 180-1112A. 3466 records from (Table 3) Distribution of benthic foraminifers at DSDP Hole 21-206. 288 records from Phytoplankton abundance at several bottle stations in May 1996, Sechura, Peru. 10 records from Oberservation of birds at station PS14/143 along 49° West. 864 records from Caracterizando la diversidad de especies con códigos de barras del ADN en un grupo de avispas parasitoides: un caso de estudio en un área natural protegida mexicana. 10 records from (Figure 9) Relative abundance of nannoliths at DSDP Hole 62-465A. 216 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 4 records from Duocrassana longula, new genus and species of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae) from southern Mexico and its relationship to other genera in Athysanini. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 54 records from Biotope im Schulumfeld. 27 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5121-1. 18750 records from National Trust - Hatfield Forest species data held by The National Trust.. 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 608 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 90-594. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 15676 records from UCM Mammal Collection (Arctos). 6 records from (Table 1) Dinoflagellate cyst zonations at ODP Site 202-1233. 195 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 36 records from Ice Algae Barents Sea. 38 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto75-83. 290 records from The symphytognathoid spiders of the Gaoligongshan, Yunnan, China (Araneae: Araneoidea): Systematics and diversity of micro-orbweavers. 19 records from Pollen record from Mamontovy Klyk. 651 records from Range table from planktonic foraminifers in ODP Hole 155-940A. 15733 records from imr_mareano_beamtrawl. 2 records from Description of the puparium of Hermetia pulchra (Diptera: Stratiomyidae) from Brazil. 731 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 14 records from Description of lithologic section units of IODP Hole 325-M0047A. 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 8 records from Occurence of marine palynomorphs of sediment core CRP-1 (Table 1). 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 103 records from Birdrace-Die_Nachtigallen-Herford. 226 records from (Table A1) Annual biomass of plants and animals recorded on Bylot Island between 1993-2009. 23 records from (Table 3) Neogene relative abundances of Uvigerina spp. at DSDP Hole 95-613. 112 records from Implementación del programa de monitoreo del cocodrilo del pantano (Crocodylus moreletti) México-Belice-Guatemala: región de coordinación MXRC2-Golfo Centro, Veracruz centro y norte Oaxaca [Temporada 2013]. 5 records from Garra fluviatilis, a new hillstream fish species (Cypriniformes: Cyprinidae) from the Kwai Noi River system, Mae Khlong basin, Thailand. 134 records from Review of Lecithoceridae (Lepidoptera: Gelechioidea) in the Oceanian Region, with description of a new species and a checklist of the family. 873 records from Kartlegging av spredning av fremmede bartrær. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 57 records from Schulgarten Fichteschule. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 15 records from Urwald 2 (Bad Waldsee). 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 232 records from Distribution of planktic foraminifera of sediment trap OG5. 234 records from Size of planktic foraminifera at CTD station M39/4_352CTD-11. 39 records from Calcareous dinocysts along profile Ruegen. 3 records from Sarcodine counts and carbon biomass at station TT011_9-CTD115. 22 records from Phytoplankton abundance at bottle station GOM1/6. 171 records from Sahrbachtal Kreis Ahrweiler. 12 records from Nannofossil abundance of Hole 74-528A. 3953 records from Colección de Ostrácodos Recientes del Sur del Golfo de México (ICMyL-DF, UNAM). 57 records from Kindervilla Aussengelände/ Hiltroper Park. 492 records from Pliocene/Pleistocene benthic foraminiferal abundances from hole KR9912PC4. 67 records from Kirkegaardia (Polychaeta, Cirratulidae), new name for Monticellina Laubier, preoccupied in the Rhabdocoela, together with new records and descriptions of eight previously known and sixteen new species from the Atlantic, Pacific, and Southern Oceans. 132439 records from HBRG Insects Dataset. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 44 records from Total foraminifera counts of multinet M27/2_MSN879. 7929 records from Dinoflagellate cysts in surface sediments. 2 records from Nannofossil abundance of Hole 18-174A. 13 records from Benthic macrofauna abundance of sediment core 12930-065. 214 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano y Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 185 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Tinamidae. 173 records from (Table T3) Stable isotope ratios and abundances of foraminifera from ODP Hole 172-1063D. 68939 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 1 records from The extinct river shark Glyphis pagoda from the Miocene of Myanmar and a review of the fossil record of the genus Glyphis (Carcharhiniformes: Carcharhinidae). 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 983 records from (Table 2) Distribution of planktonic foraminifera in the larger size fraction of ODP Hole 120-747A. 18 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part I. 321 records from Fuldaaue (Stadtgebiet Fulda). 10255 records from Araneae Collection. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 59 records from Schulteich Freie Waldorfschule Darmstadt. 18 records from Smear slide analysis on sediment core GeoB4206-1. 15 records from Biodiversidad microbiana de los ecosistemas marinos en la Isla Cayo Serrana durante la Expedición Seaflower 2016. 22 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI237. 264 records from Planktic foraminifera counts of sediment core RC12-339. 137 records from Planktic foraminifera counts of sediment core V28-25. 410 records from (Table 1) Distribution of planktonic foraminifera in ODP Hole 183-1135A, Part II. 91 records from Genética y taxonomía de los robalos (Centropomus spp) del golfo de California, México. 2320 records from (Table 7) Distribution of planktonic foraminifera in the early Miocene to late Pliocene section of ODP Hole 149-899A. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 479 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P5. 804 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 376 records from Wupperaue bei Kemna (Wuppertal). 145 records from Microplankton abundance in the euphotic zone of the Levantine Sea in October-November 1991. 1059 records from Planktic foraminifera abundance of Hole 15-148. 23 records from Benthic foraminifera abundance of Hole 93-603. 14 records from Occurrence of recent nannoplankton in surface sediments at M1_MULT243, Arabian Sea (Fig. 2). 4 records from Nannofossil abundance of Hole 55-430A. 23 records from AlgaTerraMovies. 751 records from Planktic foraminifera abundance of Hole 49-408. 2 records from Two new species of Chromadoridae (Chromadorida: Nematoda) from the East China Sea. 1764 records from Arachnida of Costa Rica (INBio). 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 160 records from Total foraminifera counts of multinet M21/1_MSN607. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN658. 4 records from Zwischen Enz und Schule. 1 records from Occurrence of mammalia relicts at site Egtved. 88 records from (Figure 5) Distribution and relative abundances of microbiota recovered from the Jurassic section of DSDP Hole 79-547B. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 3769 records from Eggs Specimen. 40 records from Assemblage of living benthic foraminifera in sediment core CD146_55922#2, 63-150 µm. 1360 records from (Appendix table DR1) Foraminiferal distribution data for ODP Hole 178-1098B. 2 records from Nannofossil abundance of Hole 74-525A. 6723 records from NOAA HML Tidal Creek Database. 221 records from Foraminifera abundance of sediment core IN68-5. 1957 records from BioGIS - Marine snails - HUJ collections. 19 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-139BX. 327 records from Foraminifera abundance of Hole 58-443. 3 records from Dinoflagellate abundance of Hole 85-572. 5 records from New species of Pseudachorutes (Collembola: Neanuridae) from Northeastern Algeria. 4714 records from Colección de Anfibios. 28 records from (Table A) Wet weight night biomass of dominant mesozooplankton groups obtained from night catches within the Bismark Polygon in June 2001 and June-August 2002. 22 records from MVZ Herp Observations (Arctos). 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 95 records from Total foraminifera counts from multinet M31/2_MSN896. 1657 records from Implementación del Programa de Monitoreo del Cocodrilo de Pantano (Crocodrylus moreletti) México-Belice-Guatemala en la Región de Coordinación MXRC3-Sur: sur de Veracruz, Tabasco, Chiapas y oeste de Campeche. 10 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 521 records from Bayerische Donau - Leipheim. 2 records from Nannofossil abundance of Hole 10-87. 43 records from (Table 5) Distribution of calcareous nannofossils in DSDP Holes 92-600C and 92-601. 526 records from (Table 1) Relative abundances of calcareous nannofossils in ODP Hole 115-711A. 976 records from Mammals (NSMK-MM). 185 records from (Table 2) Abundances of dinoflagellates in ODP Hole 105-646B. 12298 records from Hongos del estado de Veracruz. 101 records from Schulgelände IGS-Frosch (Thaleischweiler-Fröschen). 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 349 records from Range table from planktonic foraminifers in ODP Hole 182-1126B. 13 records from Foraminifera abundance of Hole 57-438B. 62 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 710 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 98 records from Scolopendromorpha of New Guinea and adjacent islands (Myriapoda, Chilopoda). 1189 records from Saproxylic insects caught in window traps and hatched from polypores in small and large old forests in southern Norway. 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 506 records from Nemátodos acuáticos de vida libre de Quintana Roo. 2577 records from Shellfish (WSHN-MS). 1227 records from M. Andrew Johnston Collection. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 84 records from BIRDRACE Avinauten. 8462 records from Polish seed gene bank – historical passport data of accessions. 195 records from (Table T2) Concentrations and accumulation rates of Globorotalia menardii at ODP Hole 175-1087A. 137 records from Planktic foraminifera counts at CTD station PS55/077-1. 63 records from Microzooplankton abundance measured on water bottle samples at station PS58/108-1. 12337 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 17 records from Coccoliths in sediment core PS1527-2. 73 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Anhimidae. 17715 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 5 records from New records of Paraleptophlebia werneri Ulmer, 1920 and P. strandii (Eaton, 1901) from Finland (Ephemeroptera, Leptophlebiidae). 187 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 1 records from Nothrus doliaris. 6251 records from cmn-arctic-marine-benthos. 2513 records from Carabidae of the Tatra Mts.. 48869 records from UFP - Herbário UFP - Geraldo Mariz. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD85. 5 records from Distribution of Quinqueloculina sp. in sediment core 13200-078. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 2001 records from Biodiversidad de crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas (R53, Río San Juan y Río Pesqueria). 7120 records from Recuento de la diversidad florística de Veracruz. 1322 records from Taxonomía y sistemática de la Ictiofauna de la Bahía de Banderas del Estado de Nayarit, México. 2814 records from Anfibios y reptiles del estado de Querétaro. 21354 records from Birds Specimens. 2960 records from Herp specimens. 2930 records from Coleópteros malacodermos (Phengodidae, Cantharidae, Lycidae, Lampyridae) del estado de Veracruz, México. 236 re
Keywords: GBIF; biodiversity; species occurrences